Proteomic and metabolomic analysis of Litopenaeus vannamei infected with infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Fan Yang; Shou-Xin Luo; Zhi-Peng Yin; Ling-Jun Si; Ting Li; Lin-Rui Chang; Dong-Chun Yan (Aquaculture, 2027)

A knowledge-based retrofit priority identification framework of the mineral processing to assist in process improvement - Furong Sun; Dakuo He; Hongying Lin; Qiang Li; Chun Wang; Jiacheng Liu; Duanduan Wang (Minerals Engineering, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

First record of Brachyphyllum (Cheirolepidiaceae) from the Lower Jurassic of the Ordos Basin, China: Paleogeographic and paleoclimatic implications linked to T-OAE - Chao-Hui Wei; Yun-Feng Li; Chang-Lu Zhang; Xiao Tan; Fei Liang; Chun-Lin Sun; Tao Li; Yu-Ling Na (Review of Palaeobotany and Palynology, 2026)

Comparative impact of different freezing technologies on the quality retention of fried chicken strips - Chun Wang; Yilin Lin; Xiaoqing Li; Yue Wang; Yigang Yu (International Journal of Refrigeration, 2026)

Enhancement by Ce addition to La-Zr-mixed oxide supported Ni catalysts on the mid-temperature steam reforming of methane - Li-Chun Lin; Teng-Li Yu; Cheng-Yao Hung; Guan-Yu Chen; Yi-Ning Chao; Shawn D. Lin (Fuel, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Novel D-A1-A2-π-A self-assembled monolayer in suppressing the Voc deficit of the wide-bandgap perovskite solar cells - Dong-Tai Wu; Yu Hsuan Lin; Yi-Chen Lin; Hsin Li; Yu-Chen Liang; Yu-Tong Hung; Yi-Sheng Lin; Wei-Jia Qiu; Shi-Chun Liu; Yuan Jay Chang; Chieh-Ting Lin (Chemical Engineering Journal, 2026)

The progressive formation process of the tectono-metamorphic mélange belt: An example from the Mogutai massif, Dunhuang Orogenic Belt, Northwest China - Yichao Chen; Xue-Li Jia; Qian W.L. Zhang; Zhen M.G. Li; Hui C.G. Zhang; Hao Wang; Wenjiao Xiao; Yan-Lin Zhao; Haiquan Tang; Chang-Ming Lu; Chun-Ming Wu (Journal of Structural Geology, 2026)

A covalent organic framework with hydrazone bond for efficient enrichment of phenolic pollutants - Xiaohua Xu; Lin Hao; Weihua Liu; Qianqian Wang; Shuofeng Li; Qiuhua Wu; Chun Wang; Zhi Wang (Food Chemistry, 2026)

Intelligent theranostic nanoplatforms in next-generation precision oncology - Xiangying Deng; Chun Jiang; Ye Li; Qi Su; Kangling Xie; Lin Zhao (Chemical Engineering Journal, 2026)

Scalable cancer cell-derived liposome capable of homologous tumor-homing to encapsulate near-infrared light-responsive drug delivery nanocomposites for enhanced combination therapy - Fang-Yi Hsu; Wen-Jyun Wang; Li-Ting Yang; Yi-Zi Chen; Ting-Chi Lo; Jia-Sin Chen; Wei-Lun Huang; Yen-Liang Li; Hidenobu Takahashi; Wen-Chun Hung; Chi-Wen Luo; Shu-Yi Lin; et al. (Chemical Engineering Journal, 2026)

Epitaxial high-entropy relaxor ferroelectric films for flexible piezoelectric sensors and MEMS - Yu-En Pan; Yu-Hao Tu; Li-Hui Tsao; Yu-Ju Lin; Sheng-Yao Hung; Yi-Chun Chen; Mengyao Xiao; Qibin Zeng; Huajun Liu; Chengkuo Lee; Ying-Hao Chu (Chemical Engineering Journal, 2026)

Glycocalyx-mimetic ionotronic silk films for immunoregulatory infected wound repair and wearable motion sensing - Zi-Xian Dang; Ke Ma; Han Zhang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Coumarin constituents from Gerbera delavayi: Anti-inflammatory and anti-tumor activities with chemotaxonomic significance - Yan Zhong; Yu-Shuang Wen; Ying-Jie Xu; Chun-Hua Liu; Xue Ma; Yong-Lin Wang; Yong-Jun Li; Li Jiang (Biochemical Systematics and Ecology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Corrigendum to “Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan” [J. Asia-Pac. Entomol. 29(3) (2026)102584] - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Susceptibility of Spodoptera frugiperda to novel insecticides and detection of known target-site mutations following invasion of Taiwan - Hung-Ming Chao; Wen-Jer Wu; Li Lin; Hurng-Yi Wang; Ju-Chun Hsu (Journal of Asia-Pacific Entomology, 2026)

Condensate-boosted SOD/CAT-mimetic nanozyme reactivity for antioxidant therapy of wear particle-induced periprosthetic osteolysis - Han Zhang; Ke Ma; Zi-Xian Dang; Chun-Ning Bi; Yu-Ting Li; Ke-Zheng Chen; Sheng-Lin Qiao; Yong-Tao Zhang (Chemical Engineering Journal, 2026)

Lactococcus cremoris subsp. sagaensis subsp. nov., Isolated from Naturally Fermented Yogurt - Lin Cheng; Tian-Xue Wang; Chun Yan Li; Chaoxin Man; Chun Tao Gu (Current Microbiology, 2026)

Context-dependent coupling between rhizosphere biochemical activation and SOC enrichment in croplands: a global meta-analysis - Ya-Jun Cheng; Jie-Yu-Xin Kang; Chun-Yan Li; Bai-Jian Lin; Yun Zhang; Jian-Ying Qi (Plant and Soil, 2026)

The JAK/STAT pathway: a pivotal therapeutic target in disease and advances in natural product modulation - Ming-Yue Li; Yu-Yang Lin; Chun-Ying Wang; Yu-Shan Qi; Jun-Sheng Zhang; Di Ge; Hai-Na Yu; Hua Zhang; Jie Bao (Molecular Diversity, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Atomically precise ferrocene-based Fe/Mn nanocluster for solar-driven cycloaddition of epoxides with carbon dioxide - Xue-Feng He; Chun-Yang Li; Yu-Lin Jiang; Wan-Yu Zhu; Qiu-Hong Cheng; Kun Huang; Da-Bin Qin; Xiang-Yu Zhang (Chemical Engineering Journal, 2026)

Aging-Related Changes in the Injury Response of the Peripheral Nervous System - Yue-Yan Cen; Mu-Yun Wang; Qin-Xuan Song; Xin-Lin Gao; Cheng Zhou; Chun-Jie Li; Fei Liu; Yan-Yan Zhang; Jie-Fei Shen (Neuroscience Bulletin, 2026)
Peripheral nerve injury (PNI) significantly impairs patients’ quality of life, with elderly individuals experiencing particularly severe consequences due to aging-related declines in neuronal injury response and repair capabilities. Processes of the generation and transmission of injury signals, axonal disruption, initiation of regeneration, and the elongation of regenerating axons, as well as the subsequent reinnervation by these axons, are all significantly influenced by aging. These alterations are closely associated with changes in mitochondrial function, neuronal transport systems, a persistent inflammatory milieu, and various microenvironmental non-neuronal cells. Therefore, this review synthesized the pivotal role of aging in the multifaceted regulation of the nervous system following PNI and highlighted promising molecular regulatory mechanisms in the signaling pathways. Furthermore, it identified critical areas for future research, including unresolved questions in age-associated injury responses, potential targets for pharmacological intervention, and emerging therapeutic strategies meriting consideration for research and development.

Infection risks associated with b/tsDMARDs in rheumatoid arthritis: a systematic review and network meta-analysis - Xue-Mei Zhang; Li Liu; Yi-Dan Yan; Zai-Li Zhang; Ke-Jia Le; Yang-Xi Liu; Xiao-Jun Ni; Liang-Jing Lu; Guo-Hua Zhou; Zhi-Chun Gu; Jia Li; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2026)

Assessing Taiwan's Future Climate: High Resolution Projections and Regional Impacts From Statistical Downscaling of CMIP6 Data - Cheng‐Ta Chen; Yu‐Shiang Tung; Chun‐Yu Wang; Shiou‐Li Lin (International Journal of Climatology, 2026)
This study explores how Taiwan's climate might change in the future, using statistical downscaling techniques to make global climate projection data more relevant to the region. Global climate models often lack the fine detail necessary for small areas, such as Taiwan, particularly given its unique geography and local weather systems. To address this, we used statistical methods to create high‐resolution projections that combine local weather observations with data from the latest international climate model data archive (CMIP6). These projections cover daily temperature and rainfall patterns from the past (1960–2014) and into the future (2015–2100) under four different future socioeconomic and climate change scenarios. Our findings demonstrate that the downscaling method effectively corrects historical temperature and precipitation biases, yielding a robust signal for temperature projections and moderate uncertainty for precipitation trends, compared to low‐resolution climate model simulations. Taiwan is expected to experience significantly warmer temperatures, with heatwaves lasting longer and extremely high temperatures becoming increasingly common by the end of the century. Rainfall patterns are also expected to change, with heavier rain during wet seasons and longer dry spells. Central and southern Taiwan, in particular, are likely to experience more intense rainfall events, thereby increasing the risk of flooding. At the same time, drier regions could face more frequent and severe droughts. This research provides a clearer picture of Taiwan's future climate and offers valuable information for planning ways to adapt to these changes. The detailed climate projection dataset bridges the gap between global climate models and regional applications, providing essential local‐scale climate information for decision‐makers and researchers in fields such as hydrology, forestry and water resource management.

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Nine previously undescribed immunosuppressive ent-labdane diterpenoids from the roots of Eurysolen gracilis - Lin-Lin Teng; Yan-Chun Liu; Chao-Jiang Xiao; Shu-Xi Jing; De-Sen Li; Ran Xu; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Mean warming enhances insect resilience to high temperatures: species-specific evidence from two wheat aphids - Xue-Jing Wang; Yu Wang; Shu-Lin Ning; Jia-Qi Li; Biao Cui; Long-Fei Yue; Li-Yan Wang; Chun-Sen Ma (Journal of Insect Physiology, 2026)

Metamorphic evolution and geochronology of garnet amphibolite, the Dongbatu tectonic-metamorphic mélange, eastern middle Paleozoic Dunhuang Orogenic Belt, northwest China - Xue-Li Jia; Yichao Chen; Yan-Lin Zhao; Zhen M.G. Li; Hui C.G. Zhang; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Pollutant-specific pathways linking gaseous air pollution to adolescent depressive symptoms: Direct and sleep-mediated effects in a population-based retrospective cohort study - Chun-Ji Lin; Po-Ya Chang; Yu-Ling Li; Chih-Da Wu; Chao-Ying Tu; Chih-Yi Wu; Szu-Ying Chen; Hung-Yi Chiou (Environmental Research, 2026)

Polyacrylamide based hydrogel with high temperature and salinity tolerance: the role of aminated distilled spent grain - Xue-Li Long; Kang-Lin Chen; Hong-Ke Yang; Hong-Li Dong; Hong-Kui He; Li-Chun Dai; Zu-Guo Yang; Zhi-Xiang Xu (Biomass and Bioenergy, 2026)

Host-derived Bacillus velezensis enhances intestinal structure, antioxidant capacity, and pathogen resistance in the American bullfrog (Aquarana catesbeiana) - Yueming Hu; Han Lin; Mengzhen Jiang; Changyi Lin; Hua Li; Jingyang Sun; Kesong Chen; Yebing Yu; Chun Liu (Archives of Microbiology, 2026)

Heteronemin suppresses chemoresistant oral squamous cell carcinoma cells through ROS-mediated apoptosis and cuproptosis-associated mitochondrial stress - Chiung-Wei Huang; Fan-Li Lin; Chun-Feng Chang; Hsiao-Hsuan Huang; Wan-Ju Wu; Hui-Min Chang; Mei-Ying Lin; Jue-Liang Hsu; Shih-Ya Hung; Chien Hsing Lee (Apoptosis, 2026)

Effect of Excavation Sequence and Bolt Support on Surrounding-Rock Stability of a Double-Tunnel System in Jointed Rock Mass - Feng Jiang; Tian-lin Huang; Hai-zhen Huang; Ji-song Wang; Peng He; Gang Wang; Chun-gui Li; Ting-fang Liu; Cheng-cheng Zheng; Zhi-yong Xiao (Applied Geophysics, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Climate change and pesticide resistance: a synthesis on emerging mechanisms and evolutionary dynamics - Chun-Sen Ma; De-Xian Li; Jin-Chen Wei; Qing-Cai Lin (Current Opinion in Insect Science, 2026)

Pt(II) complexes with narrow-spectrum emission for high-performance green organic light-emitting diodes - Qinghua Xia; Yong Cao; Yihan Chu; Yang Li; Xuanbo Hu; Jinyu Song; Cong Zhang; Xiao-Chun Hang; Lin Xu (Chemical Engineering Journal, 2026)

The Dorsal CA2 to Ventral CA1 Circuit Contributes to Spatial and Context-Dependent Memories - Ning Li; Bingqing Zhao; Xiaowen Shen; Hua He; Jianxiang Zhou; Jing Zhang; Lin Xu; Xiaochun Chen; Chun Xu (Neuroscience Bulletin, 2026)

Catalase is a critical virulence factor in Aeromonas schubertii infection of snakehead fish (Channa argus) - Mengzhen Jiang; Haiyan Gong; Qing Wang; Han Lin; Yueming Hu; Hua Li; Jingyang Sun; Kesong Chen; Biao Jiang; Wei Li; Youlu Su; Chun Liu (Antonie van Leeuwenhoek, 2026)

Mechanical Properties of Glycated Cracked Articular Cartilage Under Uniaxial and Cyclic Tensile Loading - Li-Lan Gao; Yi Fang; Xiang-Long Lin; De-Zhao Kong; Yan-Song Tan; Rui-Xin Li; Kai Sun; Chun-Qiu Zhang; Yanliuxing Yan (Annals of Biomedical Engineering, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Effects of Boron on the Lipid Metabolism, Estradiol Concentration, Uterine Morphology and ERα Expression in Ovariectomized Rats - Ziyan Li; Qinglan Liu; Lin Wang; Chun Wang; Long Wang; Shenghe Li; Qianqian Hu (Biological Trace Element Research, 2026)

Multiprotein-based nanomedicines with dual CD44/CD133 targeting and GSH-responsive drug release for improving cancer chemotherapy - Lu-Yi Yu; Pei-Wei Shueng; Yu-Hsin Wang; Yu-Wei Yen; Kuan-Wei Chen; Chieh-Ru Li; Hsin-Cheng Chiu; Yu-Wen Lin; Chun-Liang Lo (Drug Delivery and Translational Research, 2026)
Albumin, a highly biocompatible protein, has been utilized in the construction of anti-cancer drugs for the treatment of various cancers. However, albumin-based nanomedicines still face several clinical challenges, including low stability in the bloodstream, non-specific targeting ability, and lack of controlled release capability. To address these limitations, we developed a multiprotein-based nanomedicine for targeted chemotherapy of non-small cell lung cancer (NSCLC). This nanomedicine was assembled using a heart-shaped albumin and two Y-shaped anti-CD44 and anti-CD133 antibodies. To enhance stability and improve therapeutic efficacy, the multiproteins were crosslinked using disulfide bond linkers and loaded with paclitaxel and ceramide. This resulted in nanomedicines that exhibited responsiveness to glutathione (GSH) and demonstrated inhibition of tumor cancer cells and cancer stem cells (CSCs). Our experimental results indicated that the inclusion of anti-CD44 and anti-CD133 antibodies enhanced the targeting capability of nanomedicines towards cancer cells and CSCs in an in vitro study and the accumulation in both normoxic regions and hypoxic niches in in vivo tumor xenografts. The multiprotein-based nanomedicines also demonstrated GSH-dependent drug release behavior, induced apoptosis in cancer cells and CSCs, inhibited cell migration, and effectively suppressed NSCLC tumor growth. Overall, our findings presented a novel nanostructure created from differently shaped proteins for application in drug delivery. This multiprotein-based nanomedicines showed promising potential in addressing the limitations of albumin-based nanomedicines and may offer improved therapeutic outcomes for cancer treatment. Graphical Abstract

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Possible inter-room aerosol-mediated COVID-19 transmission in a quarantine hotel: A case study - Merrill LIM; Junjing YANG; Sze Tat TAN; Man XIAO; Chun Ping GAO; Vernon LEE; Yee Leong TEOH; James CHAN; Lin CUI; Yichen DING; Joanna SHEN; Ruixin LI; et al. (Building and Environment, 2026)

Quantitative study on the cave environmental factors for the fractionation of stable oxygen isotopes during the deposition of speleothem - Yue Jin; Chun-Jie Wang; Jian Zhang; Wen-Jun Sun; Chao-Jun Chen; Yao Wu; Hua-Yan Li; Yue-Hua Xiang; Yue-Yuan Lin; Xin-Rui Ye; Xin-Yan Li; Zhong-Lin Deng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Geochemistry of tourmaline in granitic rocks from the Zharigana and Caolong areas, Northern Tibet: Implications for the identification of lithium-mineralizing plutons - Ling Ma; Jin-Sheng Zhou; Qiang Wang; Lin Ma; Jin-Heng Liu; Wu-Fu Li; Bing-Zhang Wang; Chun-Tao Wang; Jian-Dong Liu; Xin-Yuan Zhang; Mao-Rui Liu; Zhi-Wei Yu; et al. (Lithos, 2026)

16S rDNA sequencing combined with non-targeted metabolomics profiling reveals the mechanism of simulated digestion ultra-sound pea protein isolate in vitro - Xinyu Zhao; Xuemei Dong; Jianke Fang; Chun Li; Lin Zhao; Guofang Zhang; Peng Du; Tong Zhang; Xinyao Sun; Libo Liu; Wenkui Guo (Food Bioscience, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

Effects of glycyrrhizic acid on growth performance and hepato-intestinal health of American bullfrogs (Aquarana catesbeiana) - Zhixiang Bai; Kesong Chen; Xingye Xu; Han Lin; Jingyang Sun; Hua Li; Yueming Hu; Mengzhen Jiang; Wensen Tan; Yanwen Wu; Yebing Yu; Chun Liu (Aquaculture International, 2026)

Isolation and biological evaluation of a novel steroid from Sagina japonica (Sw. ex Steud.) Ohwi - Jun-Hong Liu; Qian-Lian Yin; Xue Li; Mei Qing Zhang; Lin Guo Zou; Xin Jian Song; Li Jiang; Chun Hua Liu; Yong Jun Li (Natural Product Research, 2026)

Magnetoelastomer-based grain flow sensor for combine harvesters - Xin-Dong Ni; Mao-Lin Li; Fang-Lei Li; Zi-Xuan Dai; Chun-Xiao Xing; Feng Wang; Yan-Xin Yin; Du Chen; Zhi-Zhu He (Computers and Electronics in Agriculture, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Diverse metamorphic P‒T‒t paths of the Mogutai tectono-metamorphic mélange, eastern Paleozoic Dunhuang Orogenic Belt, northwestern China - Yan-Lin Zhao; Yichao Chen; Xue-Li Jia; Hui C.G. Zhang; Zhen M.G. Li; Longxiang Quek; Chun-Ming Wu (Journal of Asian Earth Sciences, 2026)

Body size- and water homeostasis-dependent temperature stress tolerance and transcriptional changes in red fire ant workers - Wei Gao; Rui Peng; Jian-min Yang; Jian-lin Lu; Hong-yun Cao; Ying-huan Li; Chun Li; Wen Fu; Jin Xu (Journal of Asia-Pacific Entomology, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

3D-printing of hierarchical porous monoliths using emulsion gels stabilized by lignin-containing cellulose nanofibrils for thermal insulation - Chuhang Liu; Xiaojie Shi; Bo Lin; Zekun Song; Feng jiang; Mei-Chun Li; Chaozheng Liu; Changtong Mei (Carbohydrate Polymers, 2026)

Oligochitosan‐Ameliorated Gut Microbiome and Metabolic Homeostasis in Hybrid Groupers ( Epinephelus lanceolatu ♂ × Epinephelus fuscoguttatus ♀) Infected With Vibrio harveyi - Fei Shi; Lixin Ma; Zhilong Chen; Zhuojin He; Xiaomin Zheng; Cuiyun Zou; Chun Liu; Li Lin (Journal of Fish Diseases, 2026)
Vibrio infections cause enteritis in grouper fish, leading to high mortality and stunted growth, which is a major challenge for aquaculture. Oligochitosans, marine prebiotics with bioactive properties, have proven their potential for growth promotion and immune regulation. However, the impacts of Vibrio harveyi on the gut microbiome of grouper fish and the potential of oligochitosans to modulate these effects remain poorly understood. This study investigates the influence of oligochitosan on the gut morphology, microbiota and metabolic patterns of hybrid grouper following low‐dose infection with V. harveyi . After 8 weeks of feeding, infected groupers exhibited histopathological changes in the intestine that were mitigated by oligochitosan, as evidenced by improved villus height and intestinal wall thickness. Microbiome sequencing revealed that oligochitosan enhanced α‐diversity and shifted bacterial communities, particularly increasing the abundance of Fusobacteriota and Actinobacteriota . Furthermore, the prevalence of Shewanella and Vibrio , which were more abundant in infected groupers, was reduced upon oligochitosan treatment. Metabolomic analysis indicated that lipid metabolism pathways were significantly altered in response to infection and oligochitosan intervention. Overall, oligochitosan modulates the gut microbiome and metabolite profiles, potentially protecting against V. harveyi ‐induced intestinal dysbiosis and metabolic disorders in hybrid groupers.

Effects of temperature change pattern on the hatching of zooplankton resting eggs and community structure - Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Han Zhu; Yi-Long Xi (Hydrobiologia, 2026)

Mechanisms of cell death in Klebsiella pneumoniae-induced acute splenic injury in Aquarana catesbeiana - Han Lin; Hua Li; Kesong Chen; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Synergistic pathogenic mechanisms of EHP and IHHNV co-infection in Litopenaeus vannamei: Insights from RNA-seq analysis - Lin-Rui Chang; Cai-Yi Chen; Fan Yang; Chuan-Yu He; Fan Li; Ting Li; Ling-Jun Si; Dong-Chun Yan (Journal of Invertebrate Pathology, 2026)

The bioaccumulation characteristics and combined toxicity effects of aged microplastics with adsorbed Hg(II) in oysters - Lianghong Li; Chun Lv; Qijia Zhou; Qiaoguo Tan; Haiying Lin; Qingge Feng; Xiaohong Song; Xianghua Wu; Qiuyan Hu; Lixin Huang; Jie He; Guanjian He; et al. (Journal of Hazardous Materials, 2026)

Interpretable multi-task dual-attention model for forecasting heating load and supply water temperature in district heating systems - Yingfeng Lin; Chun-E Huang; Chunwang Li; Hui Wang; Chuanzhao Zhang (Energy and Buildings, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Engineering phototrophic cyanobacteria as a robust platform for production of plant-derived bioactive terpenoids - Hui-Cheng Feng; Chun-Lin Tan; Xiang-Mei Zheng; Xin Yu; Jonathan Gershenzon; Sheng-Hong Li; Yan Liu (Chemical Engineering Journal, 2026)

A microenvironment-responsive chitosan based injectable hydrogel with synergistic anti-inflammatory effects of triptolide and copper ions for spinal cord injury repair - Han-Jian Hu; Zhenming Tian; Zeng-Lin Li; Chun Cheung Chan; Hongyan Zhang; Shipeng Tang; Yu Chen; Zhaoyin Chen; Tian Hu; Bin Liu; Gang-Biao Jiang (Carbohydrate Polymers, 2026)

Beyond the check-up: how well-child exams, pediatric specialists, and provider recommendations can close HPV vaccine gaps for Chinese American Teens - Lin Zhu; Xinrui Li; Elaine Zhiqing Liu; Philip T. Siu; Shumenghui Zhai; Chun Pan; Nikki Cao; Grace X. Ma (Cancer Causes & Control, 2026)
Purpose This study aimed to identify provider- and practice-level factors influencing human papillomavirus (HPV) vaccine uptake among Chinese American (CA) adolescents. Despite increasing public health efforts, HPV vaccination rates in this population remain suboptimal, and knowledge on the link between provider/practice characteristics and vaccine uptake is limited. Methods We analyzed data from 1,272 CA adolescents (aged 13–17) using the National Immunization Survey-Teen (2015–2019) datasets. Key measures included HPV vaccine initiation and completion (based on proxy reporting and verification), accompanied by various multilevel factors: provider-level (recommendation, specialty), practice-level (facility type, vaccine acquisition, well-child exam), parent-level (mother’s education, marital status), and adolescent-level characteristics. Weighted descriptive statistics and stepwise multivariate logistic regression were used to examine associations. Results Overall, 71.22% of CA adolescents initiated at least one HPV vaccine dose, while 48.14% completed the regimen. Provider's recommendation (initiation OR = 21.50, completion OR = 8.12), having a pediatrician (initiation OR = 5.37, completion OR = 3.20), and receiving the 11–12-year-old well-child exams significantly predict both initiation and completion. Regional disparities were observed, with adolescents in the Northeast and West showing higher completion rates than those in the South. Unexpectedly, adolescents not enrolled in school and those with mothers who had less than 12 years of education or were unmarried showed higher completion rates. Conclusion Provider recommendations and pediatric care are crucial for improving HPV vaccination rates among CA adolescents. Addressing regional disparities and implementing targeted interventions, including enhanced provider training focused on culturally sensitive communication, are essential to dismantle systemic barriers and improve comprehensive vaccination coverage in this underserved population.

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

Mechanisms of bioelectrochemistry enhanced saline aerobic granular sludge: From EPS monomers to microbial metabolism - Aqiang Ding; Shikang Li; Wenkai Yao; Yuhao Tong; Lin Quan; Chun Yang; Fuzhong Song; Daijun Zhang; Peili Lu (Chemical Engineering Journal, 2026)

Hippocampal Neuronal Ferroptosis Driven by Lipocalin-2 Mediates Comorbid Visceral Pain and Anxiety in Irritable Bowel Syndrome - Ying Tang; Zhengqing He; Qianli Zhang; Yiqian Liu; Lu Li; Yu Chen; Aiqin Chen; Chun Lin (Molecular Neurobiology, 2026)

Corrigendum to “Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk” [Toxicology and Applied Pharmacology Volume 503, October 2025, 117465]. - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Spatiotemporal pattern of vegetation evolution in northeastern Tibetan Plateau during the Cenozoic and its climatic significance - Yun-Xia Jia; Wen-Chao Zhang; Li-Jun Tian; Zhi-Lin He; Zhao Wang; Qing-Chun Tian (Palaeoworld, 2025)

Whether the hybridization of polystyrene, polyethylene, and polypropylene microplastics impacts aquatic carbon leakage from water hyacinth: A case study considering per(poly)fluorocarboxylicacid cocontamination - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Chun Wang (Journal of Environmental Chemical Engineering, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

Novel self-assembled antimicrobial peptide Pardaxin hydrogel as a functional biomaterial for food packaging and preservation - Sanjay Prasad Selvaraj; Ju-Chun Chang; Karukuvelraja Raja; Jing-Ting Zhu; Prakash Kishore Hazam; Wen-Chun Lin; Jung-Ren Huang; Tsung-Lin Li; Jyh-Yih Chen (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

CO2-mediated SEI engineering via Li2C2O4 pre-lithiation: A dual-functional strategy for high-stability SiOx/Gr anodes - Lifan Wang; Peng Han; Lin Zhang; Cong Zhong; Min Chen; Ruixiang Li; Yiheng Wu; Zhengping Zuo; Xindong Wang; Xuefeng Wang; Chun Zhan; Guicheng Liu (Chemical Engineering Journal, 2025)

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

The connection between skeletal muscle and spinal canal membrane of Takifugu rubripes and its anatomical and physiological significance - Yang Song; Wen-Bin Jiang; Yu-Yu Xiong; Chun-Zhuo Shi; Hua-Xun Lai; Jing-Xian Sun; Lin-Lin Chen; Bo Liu; Yan-Yan Chi; Ji-Hang Li; Yi-Tong Sun; Xu-Hui Zhang; et al. (Frontiers in Marine Science, 2025)
Introduction The myodural bridge (MDB) is considered one of the circulatory dynamics of cerebrospinal fluid (CSF). Initially identified in the human neck, it has since been documented across diverse vertebrates, including fish with analogous “MDB-like” structures. The teleost Takifugu rubripes , which exhibits a high degree of genetic homology with humans, serves as an excellent model for such comparative studies. Investigating its MDB-like structure can therefore provide a morphological basis for elucidating the mechanism of CSF circulation and its evolution during the vertebrate land–water transition. Methods In this study, the morphology, development, and ultrastructure of MDB-like structure of Takifugu rubripes were explored. Three fresh adult T. rubripes were selected for gross anatomy. After incubation, 33 T. rubripes aged 13–120 days after hatching (dah) were fixed in 10% formalin solution. The samples aged 50–120 dah were further decalcified with EDTA for histological paraffin sectioning and Masson staining. Four cases aged 106 dah were fixed with 2.5% glutaraldehyde, two of which were observed by scanning electron microscopy, and two cases were observed by transmission electron microscopy. Results Through light microscopy and electron microscopy, the results of the current study is that there are three types of fiber connections (MDB-like) between skeletal muscle and the spinal canal membrane in T. rubripes : (1) The fibers from the myocomma attach to the spinal canal membrane; (2) The epimysium connects to the spinal canal membrane directly or connects to the spinal canal membrane through reticular, filamentous fibers, or fibers emitting from the perimysium; and (3) The fibers from the end of the muscle bundle stop at the spinal canal membrane. These connections mainly exist on the sides of each vertebral interspace and may function similarly to the MDB. Discussion Developmentally, “MDB-like” structures appeared in T. rubripes hatched at 18 dah, began to transmit force at 21 dah, and may have a positive correlation in development with the muscle and spinal canal membrane. This experiment provides developmental morphological information for comparative studies on the conservation and interspecies differences of MDB in evolution and provides informational support to explore the physiological function of MDB in humans.

Hypoglycemic cucurbitane-type triterpenoids from fruits of Citrullus colocynthis - Hua-Wei Lv; Yu Wan; Wen-Lin Fan; Meng-Di Zhu; Qiao-Liang Wang; Zhong-Bo Zhou; Chang-Chun Chen; Hong Wang; Xing-Nuo Li (Phytochemistry, 2025)

Chlorholones A−H, bioactive sesquiterpenoids with diverse skeletons from Chloranthus holostegius - Zhao-Chun Zhan; Ting Lu; Hai-Shan Zhang; Mei-Ting Weng; Hui-hui Zhu; Qiang Lin; Hai-Yue Zhao; Yue-Hao Huang; Tian-Yuan Wu; Miao Wang; Yao-Lan Li; Yi-Wen Zhang; et al. (Phytochemistry, 2025)

Microplastics modulate neutrophil migration via an ROShistone lactylation positive feedback loop - Yi-li Wang; Xiao-chen Yuan; Chun-jiao Wei; Ke-yun Li; Lin-xi Zuo; Hao-yi Zhang; Rui-chen Ding; Ren Zhou; Yun-hua Zhang; Da-long Ren (Journal of Hazardous Materials, 2025)

Characterization of neutral fluids in the volcanic geothermal system under the Tatun Volcano Group, Taiwan - Yi-Chia Lu; Chyi Wang; Sheng-Rong Song; Pei-Ling Wang; Ting-Jui Song; Sachihiro Taguchi; Tsung-Ren Peng; Li-Hung Lin; Jian-Cheng Lee; Hong-Chun Li (Journal of Geochemical Exploration, 2025)

Linking source-to-sink processes, organic matter composition, and oxygen consumption on a shallow passive margin shelf sustained by small mountainous rivers - Yu-Shih Lin; Chih-Lin Wei; Yuan-Pin Chang; Jih-Terng Wang; Shu-Ying Chuang; Liang-Chi Wang; James T. Liu; Hong-Chun Li; Chieh-Wei Hsu (Geochimica et Cosmochimica Acta, 2025)

Identification of rice taste quality markers using metabolomics techniques - Jun Shu; Weidan Guo; Kangzi Ren; Xiangjin Fu; Zhao Long; Qinlu Lin; Chun Liu; Jiangtao Li (Food Chemistry, 2025)

A practical approach for assessing damage to bolted steel connections after fires and earthquakes - Heui-Yung Chang; Chi Wei Li; Chu-Tsen Liao; Ker-Chun Lin; Chi-Ming Lai (Engineering Structures, 2025)

Automated dimension estimation of bridge components using semantic segmentation and geometric fitting of point cloud data - Yu Chen; Chao Lin; Xianfeng Li; Shiori Kubo; Tatsuro Yamane; Pang-jo Chun (Engineering Structures, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

An innovative and clean strategy to recover copper resources from waste printed circuit boards: Malic acid leaching and micro-nano copper preparation - Xi-guang Li; Xin-long Li; Guang-liang Wei; Jing-tao Chen; Xiao-tian Zhao; Chun-chen Nie; Lin Li; Shuai Yan; Xiang-nan Zhu (Chemical Engineering Journal, 2025)

Fermented Soybean Pulp Alleviates Disease Progression of 5×FAD Model Mice - Chun-Yen Yang; Yu-Hsuan Liu; Ta-Chun Lin; Kuo-Hsuan Chang; Hsiu Mei Hsieh-Li (Molecular Neurobiology, 2025)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder of the central nervous system, characterized by memory loss and cognitive decline. The two main hypotheses regarding AD involve the accumulation of amyloid-β (Aβ) forming plaques and the intracellular hyperphosphorylation of tau protein, leading to the formation of neurofibrillary tangles (NFT). These processes are accompanied by neuroinflammation and oxidative stress, and eventual neuronal death. While soy foods are widely recognized for their nutritional benefits, soybean pulp (okara), the residue left over from making tofu or soybean milk, is mostly discarded as kitchen waste, despite being rich in nutrients such as dietary fiber, protein, and isoflavones. This underutilized byproduct may serve as a valuable resource for functional food development and sustainable resource use. In this study, fermented soybean pulp (FS) demonstrated neuroprotective effects. In vitro, FS at concentrations of 0.001 µg/mL and 0.01 µg/mL significantly improved cell viability in Aβ-induced HT-22 cells and reduced lipid peroxidation. Further, in vivo oral administration of FS attenuated the cognitive deficits of 5 × FAD mice, enhancing both short and long-term memory and reducing anxiety-like behaviors. Immunohistochemical analysis revealed that the FS-treated 5 × FAD mice group significantly reduced hippocampal amyloid plaque accumulation and gliosis. FS also upregulated the expression levels of brain-derived neurotrophic factor (BDNF), PSD95, and synaptophysin, while preventing hippocampal neuronal loss. Mechanistically, FS may activate the Nrf2 antioxidant pathway and NF-κB-mediated inflammation through the modulation of the Akt/GSK3β signaling axis in the hippocampus. These molecular actions likely contribute to increased antioxidant enzymes and suppressed neuroinflammatory responses. Overall, this study suggests that FS has therapeutic potential for alleviating cognitive and behavioral impairments in AD. Moreover, the repurposing of soybean pulp, which would otherwise be discarded, enhances its utilization value and supports sustainable green recycling.

The Double-Edged Effect of Connexins and Pannexins of Glial Cells in Central and Peripheral Nervous System After Nerve Injury - Yue-Yan Cen; Xin-Lin Gao; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen; Yan-Yan Zhang (Molecular Neurobiology, 2025)

Molecular mechanisms and therapeutic application of pyrogallic acid in treating multidrug-resistant Klebsiella pneumoniae infections in American bullfrogs (Aquarana catesbeiana) - Han Lin; Furong Li; Yufang Huang; Yongping Ye; Ziyan Chen; Chun Liu; Ruiai Chen (Aquaculture, 2025)

Hepatocyte mitochondrial DNA activated store-operated Ca2+ entry via Stim1/Orai1-induced podocyte injury in trichloroethylene sensitized mice: A new insight in liver and kidney crosstalk - Luo-lun Dong; Xue-qian Jia; Hai-bo Xie; Li-fu Zhu; Peng-cheng Zhou; Rui-xuan Cheng; Chun-lin Cao; Qi-xing Zhu; Jia-xiang Zhang (Toxicology and Applied Pharmacology, 2025)

New natural products from Rhododendron ciliicalyx subsp. Lyi - Chun-Lin Guo; Si-Xuan Liu; Lu Zhang; Ling Li; Yong-Fu Lu; Si-Yang Dai; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2025)

Assessment of environmental and health impacts during 3D printing of candidate polymeric materials for space additive manufacturing - Junling Li; Yi Liu; Chao Peng; Qifan Liu; Wei Zhao; Mingyuan Liu; Xinyu Du; Yongyin Yan; Yufei Song; Kaihui Xia; Chun Chen; Haijie Zhang; et al. (Journal of Hazardous Materials, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

In vitro simulated digestion and fermentation characteristics of pumpkin polysaccharides and their effects on the human gut microbiota - Kejuan Li; Chun Wang; Jiajun Li; Hongyuan Cao; Qi Li; Lihong Ge; Yuanting Zhu; Yuzhi Miao; Chen Xia; Changbin Lin (Food Chemistry, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Hollow mesoporous silica nanoparticles for enhanced immune protection in a multi-epitope vaccine against pseudorabies virus - Qun Wang; Jian-Dong Zhang; Hong-Xia Hu; Ying-Lei Zhang; Zhen Cheng; Shuang-Yan Xiao; Han Feng; Lin-Tao Li; Jing-Song Liu; Qi Su; Huan-Chun Chen; Zheng-Fei Liu (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

Establishing coastal partnerships for sustainable development in Taiwan: A case of Shanshui area, Penghu - Wen-Hong Liu; Hsiao-Chien Lee; Shingo Akaike; Li-Shu Chen; Chih-Cheng Lin; Hu Chun-Chieh; Kuei-Chao Chang (Marine Policy, 2025)

Altererythrobacter guangdongensis sp. nov. and Tsuneonella sediminis sp. nov., two novel carotenoid-producing species isolated from tidal flat sediment - Huan-Huan He; Ying Wang; Bing-Yu Li; Chun-Yan Lu; Shuai Li; Zhuo-Huan Zheng; Liang Zhang; Wen-Hui Lian; Xin-Tao Luo; Hai-Wei Lin; Lei Dong; Wen-Jun Li (Systematic and Applied Microbiology, 2025)

Dimeric citrinins diversity revealed by the deep-sea-derived Penicillium citrinum W23 - Tai-Zong Wu; Zhi-Hui He; Cheng-You Lin; You Li; Zheng-Biao Zou; Chun-Lan Xie; Tian-Hua Zhong; Xian-Wen Yang (Phytochemistry, 2025)

Cage-based hyper crosslinked polymers for the effective enrichment of fluoroquinolones from chicken and pork samples - Shuofeng Li; Qianqian Wang; Lin Hao; Zhi Li; Chun Wang; Qiuhua Wu (Chemical Engineering Journal, 2025)

From AI to action: Antimicrobial peptides engineered by generative adversarial networks (GANs)-A novel approach to combat resistant Bacteria - Chia-Wen Lai; Chung-Yen Lin; Meng-Chen Tsai; Wei-Jung Chen; Chia-Chun Hsieh; Zi-Jing Lin; Li-Jiuan Shen; Ying-Lien Chen; Lee-Jene Lai; Shu-Hwa Chen; Yang-Hsin Shih (Chemical Engineering Journal, 2025)

Plasma-Derived Small Extracellular Vesicles miR- 182 - 5p Is a Potential Biomarker for Diagnosing Major Depressive Disorder - Lin-Lin Zhu; Lian-Di Li; Xuan-Yu Lin; Jian Hu; Chun Wang; Yi-Jun Wang; Qi-Gang Zhou; Jing Zhang (Molecular Neurobiology, 2025)

Modification effects of socioeconomic, demographic, and geographic factors on the association between temperature and cause-specific mental disorders among Taiwanese population - Gerry Andhikaputra; Li-Wen Deng; Hsi-Yu Hsiao; Yu-Kai Lin; Ta-Chien Chan; Hsuan-Fu Chao; Yu-Chun Wang (International Journal of Biometeorology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

A symbiotic bacterium regulates the detoxification metabolism of deltamethrin in Aedes albopictus - Si-jia Deng; Lei Tu; Lin Li; Ju-ping Hu; Ju-lin Li; Jian-xia Tang; Mei-chun Zhang; Guo-ding Zhu; Jun Cao (Pesticide Biochemistry and Physiology, 2025)

Prussian blue anchored Fe(Ⅲ)-Tannic acid composite-mediated colorimetric and photothermal dual-mode immunosensor for the detection of tetrodotoxin - Sayed Haidar Abbas Raza; Bao-Zhu Jia; Jing-Min Li; Qin-Chun Yin; Wu-Yi Zhou; Sameer D. Pant; Hongtao Lei; Zhen-Lin Xu; Lin Luo (Food Control, 2025)

FlashSim: A novel particle-in-cell numerical model for vacuum surface flashover simulation based on finite element method - Hao-Yan Liu; Guang-Yu Sun; Yue-Lin Liu; Shu Zhang; Chang-Chun Qi; Sheng Zhou; Wen-Rui Li; Guan-Jun Zhang (Computer Physics Communications, 2025)

Revealing the Oxidative Stress-Related Molecular Characteristics and Potential Therapeutic Targets of Schizophrenia through Integrated Gene Expression Data Analysis - Xiu-Mei Zhu; Ji Chen; Hua-Jie Ba; Chun Yang; Jian-Wei Liu; Rui Guo; Shi-Lin Li; Ping Huang; Cheng-Tao Li; Su-Hua Zhang (Molecular Neurobiology, 2025)

A portable point-of-care testing platform for rapid and sensitive miRNA-21 detection for heart failure diagnosis - Qian Kai Lin; Wen Qing Sun; Bo Zhang; Qiao Ling; Yan Qian; Cheng Zhi Huang; Chun Mei Li; Na Wang (Analytica Chimica Acta, 2025)

Frog virus 3: Prevalence survey and quantitative analysis in American bullfrogs using TaqMan MGB probe real-time fluorescence quantitative PCR - Hua Li; Xiaobing Liu; Jingyang Sun; Han Lin; Kesong Chen; Yueming Hu; Mengzhen Jiang; Biao Jiang; Wei Li; Youlu Su; Qing Wang; Chun Liu (Aquaculture, 2025)

Rapid evaluation of Curcuma origin and quality based on E-eye, flash GC e-nose, and FT-NIR combined with machine learning technologies - Qiang Guo; Ming-xuan Li; Rao Fu; Xin Wan; Wen-hao Dong; Chun-qin Mao; Zhen-hua Bian; De Ji; Tu-lin Lu; Yu Li (Food Chemistry, 2025)

All-in-one and on-demand wound dressing based on a deep eutectic solvent ionic gel - Jia-Yu Yang; Yu-Lin Tsai; Ting-Hui Cheng; Yu-Lin Su; Yi-Kai Hong; Yu-Chen Lin; Da-Huei Lee; Chao-Chun Yang; Chao-Kai Hsu; Li-Chieh Kuo; Cheng-Hsin Chuang (Chemical Engineering Journal, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Ultrastructure and sense organs of ovipositors in the phytophagous gall-maker pest Ophelimus maskelli (Hymenoptera: Eulophidae) and its parasitoid, Closterocerus chamaeleon (Hymenoptera: Eulophidae) - Yuan-Hao Li; Yu-Yue Huang; Yu-Chun Huang; Xiao-Rong Tang; Wen-Ting Huang; Xia-Lin Zheng (Journal of Asia-Pacific Entomology, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

Design and Biomechanical Evaluation of a Disposable Eccentric Curette for Effective Necrotic Bone Removal in Core Decompression Surgery - Yu-Kuan Lin; Hsuan-Wen Wang; Po-Kuei Wu; Chun-Li Lin (Journal of Medical and Biological Engineering, 2025)
Purpose Osteonecrosis of the femoral head (ONFH) requires effective removal of necrotic tissue to improve surgical outcomes. Conventional curettes often fail to address clinical needs due to limitations in cutting capability, strength, and adaptability. This study introduces a disposable multi-angle eccentric curette designed to enhance necrotic bone removal during core decompression surgery. Methods The curette was designed with a stainless head featuring wavy cutting edges and oblique grooves for efficient cutting and debris removal. An eccentric rotation mechanism enabled adjustable scraping radii through incremental rotations (60°/120°/180°), forming an inverted bowl-shaped removal area. Performance was evaluated through static torsional strength and dynamic abrasion tests, along with usability assessments by seven orthopedic surgeons. Results The curette achieved average maximum torque of 849.72 ± 50.57 N-cm, exceeding the clinical benchmark of 640 N-cm. Dynamic testing over 300 simulated cycles demonstrated stable cutting performance and precise scraping, with diameter deviations remaining within acceptable limits (initial: 1.05%, final: 5.75%). Usability feedback highlighted its practicality and ease of operation, achieving a satisfaction rate of 97.6%. Conclusion This innovative design addresses critical limitations of existing tools by offering enhanced strength, adaptability, and cutting efficiency. These findings validate the curette’s potential to improve ONFH surgical outcomes.

Lifespan extension by rapamycin in Brachionus dorcas (Rotifera) is dose and developmental stage dependent - Ting Liu; Han-Bing Dong; Bao-Chun Shi; Hao-Yue Zhao; Zhao-Yun Wang; Lin Liu; Wei-Lu Li; Yi-Long Xi (Hydrobiologia, 2025)

Dynamic landslide susceptibility mapping on time-series InSAR and explainable machine learning: a case study at Wushan in the Three Gorges Reservoir area, China - Na Lin; Kai Ding; Libing Tan; Boyuan Li; Kai Yang; Chun Wang; Bin Wang; Nanjie Li; Ronghua Yang (Advances in Space Research, 2025)

Comparative analysis of kokumi effects in Ile-Leu, Ile-Ile, Leu-Leu, and Leu-Ile: Sensory, simulation, and structural insights - Jing Wu; Xuanxiang Lin; Chun Cui; Jun Li (Food Chemistry, 2025)

Synergistic modulation of electronic structure in high entropy perovskite oxide for enhanced bifuntional oxygen evolution/reduction reactions and its mechanistic insights via in-situ analyses and density functional theory calculation - Thi Xuyen Nguyen; Chih-Heng Lee; Jun-Hong Sun; Chun-Kuo Peng; Wen-Hui Chu; Hamed Pourzolfaghar; Yu-Ru Lin; Muhammad Ghufron; Yuan-Yao Li; Yu-Hao Chang; Yan-Gu Lin; Hsin-Yi Tiffany Chen; et al. (Chemical Engineering Journal, 2025)

Association of cold weather and influenza infection with stroke: a 22-year time-series analysis - Zihan Yang; Yuchen Wei; Xiaoting Jiang; Conglu Li; Guozhang Lin; Yawen Wang; Ka Chun Chong (International Journal of Biometeorology, 2025)
Despite the significant adverse health effects and economic burden of stroke inpatients, there has been a paucity of research specifically analyzing and quantifying the association between meteorological factors, air pollutants, influenza infection, and stroke admissions. This study assessed the impact of environmental factors and influenza activity on stroke admissions in Hong Kong from 1998 to 2019, utilizing population-based records. We employed the number of weekly stroke admissions as the primary outcome measure and matched the number with meteorological factors and air pollutant concentrations. Strain-specific influenza-like illness-positive (ILI+) rates were used as a proxy indicator of influenza activity. A quasi-Poisson generalized additive model in combination with a distributed-lag non-linear model (DLNM) was employed to elucidate the relationship of interest. Over the 22-year period, a total of 1,170,882 stroke-related admissions were recorded in Hong Kong. The cumulative adjusted relative risk (ARR) of stroke admission was significantly increased (cumulative ARR = 1.106, 95% CI, 1.069–1.143) at the 5th percentile of temperature (i.e., 15.08 °C) compared with the median reference level. Using zero as the reference value, the cumulative adjusted relative risks of stroke admission were 1.030 (95% CI, 1.018–1.042) at the 95th percentile of ILI + A/H1N1 rate, and 1.022 (95% CI, 1.007–1.038) at the 95th percentile of ILI + total rate. In conclusion, cold weather and influenza infection are risk factors to stroke admissions. Public health strategies for preventing stroke should be considered such as advocating influenza vaccination programmes during winter.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Dietary supplementation with Pediococcus pentosaceus promotes resistance to betanodavirus and ranavirus in giant groupers - Chun-Kuei Chang; Zhe-Li Lin; Yu-Hsuan Kai; Mu-Yun Peng; Yu-Chi Wu (Aquaculture, 2025)

Biodegradation of skatole by Bacillus subtilis GDAAS-A32 and its inhibition for odor emissions from swine manure - Jing-Yi Hu; Xue-Ying Han; Hong-Pin Chen; Jia-Zhou Li; Zhi-Lin Wang; Xiao-Chun Luo; Jun-Jin Deng (Journal of Environmental Chemical Engineering, 2025)

Boosting photocatalytic hydrogen evolution from binary mixture of hydrophilic-hydrophobic conjugated polymer dots with variable saponification degrees and molecular weights - Khanh Do Gia Huynh; Yu-Ting Huang; Meng-Che Tsai; Islam M.A. Mekhemer; Jayachandran Jayakumar; Yu-Tung Lin; Chun-Hao Li; Swatilekha Pratihar; Tse-Fu Huang; Dung Chau Kim Hoang; Shang-Da Yang; Ho-Hsiu Chou; et al. (Chemical Engineering Journal, 2025)

A Rare Patient of SEZ6L2 Antibody–Associated Cerebellar Ataxia - Chen-hui Cao; Wen-li Li; Yao Zhang; Ting Wei; Chun-lin Yang; Xiao-li Li; Bin Liu (The Cerebellum, 2025)

Enhanced virulence of Acinetobacter johnsonii at low temperatures induces acute immune response and systemic infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Jingyang Sun; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Veterinary Microbiology, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Exploring the influence of PCB exposure on neonatal birth outcomes and neurobehavioral development after 15 years of prohibition - Tzu-Hsuen Yuan; Chun-Ju Tai; Cheng-Hsien Tsai; Jien-Wen Chien; Akifumi Eguchi; Chih-Yun Li; Ching-Wen Lin; Chisato Mori; Chang-Chuan Chan (Environmental Pollution, 2025)

Plant diversity increases diversity and network complexity rather than alters community assembly processes of leaf-associated fungi in a subtropical forest - Jie Li; Xing-Chun Li; Hui-Yun Gan; Yue Zhang; Zi-Xuan Guo; Yu-Xuan Liu; Yong-Qing Lin; Liang-Dong Guo (Science China Life Sciences, 2025)

Detecting monogenic disorders in utero non-invasively based on fetal nucleated red blood cells highly-purified by multi-functional magnetic nanoparticles - Lin Cheng; Chun Feng; Ke Wu; Zixiang Wang; Wentao Zhu; Ting Geng; Naiqi Li; Jiawei Kang; Jie Duan; Jin Li; Yuqi Shao; Saisai Yang; et al. (Analytica Chimica Acta, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

The overlooked shadow killer: Elizabethkingia anophelis as a potent pathogen in American bullfrogs (Aquarana catesbeiana) - Chun Liu; Han Lin; Jie Ma; Yebing Yu; Ruinan Wang; Xinyi Tang; Jingyang Sun; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin (Aquaculture, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Uncovering characteristic and enantiomeric distribution of volatile components in Huangshan Maofeng and Zhejiang baked green teas - Yu-Hui Zhang; Pan-Deng Lei; Yong Ding; Xiao-Ting Zhai; Xiao-Chun Wan; Wei-Xuan Li; Yue Zhang; Hai-Peng Lv; Zhi Lin; Yin Zhu (Food Chemistry, 2025)

Evidence of lower age, fast growth, and shrinking habitat in critically endangered croaker fish Larimichthys crocea - Chien-Hsiang Lin; Tai-Yan Lin; Aafaq Nazir; Yen-Chun Wang; Pei-Ling Wang; Yoshiyuki Iizuka; Kuang-Ti Li; Ming-Tsung Chung; Jen-Chieh Shiao (Estuarine, Coastal and Shelf Science, 2025)

Research progress on the preparation of high-value carbon materials by biomass pyrolysis - Pan Li; Yasen Chen; Yucheng Lin; Wei Chen; Junhao Hu; Wei Yang; Chun Chang; Shusheng Pang (Biomass and Bioenergy, 2025)

Light-emitting diodes affect plantlet growth of Spathiphyllum cannifolium by regulating photosynthesis and sucrose metabolism during ex vitro rooting - Shuo Yu; Kui-Hua Li; Hang-Lin Song; Yue Dai; Yin-Ji Jiang; Mei-Yu Jin; Xuan-Chun Piao; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Concentration-dependent effect of norfloxacin on iron toxicity in the intestine of large yellow croaker Larimichthys crocea (Richardson, 1846) - Lin Zeng; Yong-Hong Wang; Chun-Xiang Ai; Bin Liu; Min-Hui Yu; Hui Zhang; Fei Li (Frontiers in Marine Science, 2025)
This study explores the effects of norfloxacin (NOR) on oxidative damage, iron (Fe) transport, energy metabolism, and immunotoxicity in the intestine of large yellow croaker under Fe stress. The fish were subjected to Fe (180 μg/L), low-dose NOR (1.8 μg/L, LNOR), high-dose NOR (180 μg/L, HNOR), Fe plus LNOR, and Fe plus HNOR for 60 days. These results demonstrated that Fe alone exposure increased malondialdehyde (MDA), protein carboxylation (PC), and mortality rate, and impaired intestinal tissue, which was related to the increment of Fe accumulation. Compared to Fe alone exposure, Fe plus LNOR exposure decreased MDA, PC, and mortality rate, and alleviated intestinal malformations by improving Fe transport, energy metabolism, anti-inflammatory response, and protein folding protective effect, and reducing pro-inflammatory response, indicating that LNOR had an antagonistic effect on Fe toxicity. Compared to Fe alone exposure, Fe plus HNOR exposure elevated MDA, PC, and mortality rate, and deteriorated intestinal malformations by inhibiting Fe excretion, energy metabolism, anti-inflammatory response, and protein folding protective effect, and enhancing pro-inflammatory response, indicating a synergetic effect between HNOR and Fe stress. These findings suggested that NOR had a dose-dependent effect on Fe-toxicity to large yellow croaker, which contributes to revealing the molecular mechanisms behind their interaction and its ecological implications.

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Sophflarines B−E, four distinctive matrine alkaloids from Sophora flavescens with potential neuroprotective activities - Ding Luo; Qian Xie; He Tian; Xin-Kai Zheng; Jia-Wen Zou; Yue-Hao Huang; Yan-Jun Chen; Chun-Lin Fan; Li-Jun Hu; Jian-Xin Chen; Hao Wang; Guo-Cai Wang; et al. (Phytochemistry, 2025)

Z/E configuration controlled by a Taxus sesquiterpene synthase facilitating the biosynthesis of (3Z,6E)-α-farnesene - Xue Tang; Xian-Jing Zhang; Jing-Feng Pan; Kai Guo; Chun-Lin Tan; Qiao-Zhuo Zhang; Li-Ping Long; Rui-Feng Ding; Xue-Mei Niu; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

Recent progress on triterpenoid derivatives and their anticancer potential - Zi-Xuan Zhao; Qiong-Yu Zou; Ying-Hong Ma; Susan L. Morris‐Natschke; Xiang-Yuan Li; Lin-Chun Shi; Guo-Xu Ma; Xu‐Dong Xu; Mei‐Hua Yang; Zi-Jian Zhao; Yuan-Xiang Li; Jing Xue; et al. (Phytochemistry, 2025)

Efficient removal of levofloxacin by FeCo2O4@C-REC activated peroxymonosulfate: Performance and mechanism - Bai-Hang Zhao; Bao-Yu Zhang; Bing-Lin Zhang; Jing Zhang; Chun Wang; Ye Li (Journal of Water Process Engineering, 2025)

Methane seepage leads to a specific microplastic aging process in the simulated cold seep environment - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Bin Wang; Can-Rong Li; Yi-Lei Lin; Yong-Ji Huang; Song Zhong; Xiao-Chun Zhang; Jun-Lin Hu; Si Zhang (Journal of Hazardous Materials, 2025)

The feasibility of batch-wise polyester degradation and recycling using recombinant Escherichia coli expressing PHB depolymerase (PhaZ ) - Yen-Chun Lin; En Ze Linda Zhong-Johnson; Anthony J. Sinskey; Si-Yu Li (Journal of Environmental Management, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

Geotrichum candidum AGRC-GC1 prevented the decay of pulp from Citri Reticulatae Pericarpium production by inhibiting the growth of spoilage microorganisms - Xue-Ying Han; Jing-Yi Hu; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li; Shuang Li; Jun-Jin Deng (Food Bioscience, 2025)

Inactivation of Salmonella Typhimurium on mung bean seeds by combined application of microbubbles and disinfections and its effect on sprouting - Hsiu-Ling Chen; Shih-Kao Chou; Rachelle D. Arcega; Chih-Yao Hou; Jong-Shinn Wu; Chih-Tung Liu; Chun-Ping Hsiao; Li-Yun Hung; Chia-Min Lin (Food Control, 2025)

Surface chemistry regulation enables highly durable superhydrophobic coatings with environmental robustness and pH-triggered recoatability - Mei-Lin Guo; Fang Wang; Ren-Yi Sun; Chun-Bo Li; Jin-Le Li; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Ion mitigation and strain regulation with 2D Semi-Metals for MA-Based perovskite materials in highly efficient solar cells - Chintam Hanmandlu; Soumallya Banerjee; Abhishek Kumar; Zeeshan Alam Ansari; Ramesh Kumar; Yen-Yu Wang; Lin- Chyn Yuan; Shenghan Li; Raman Sanker; Chandra Shekar Gantepogu; You-Yun Wen; Shyam Narayan Singh Yadav; et al. (Chemical Engineering Journal, 2025)

Identification of a dual functional betulinic acid analog for the treatment of osteoarthritis by phenotypic screening - Ze-Min Lin; Mai Xiang; Wen-Hui Wei; Shu-Hui Fan; Li Chen; Jie Wang; Xiao-Qian Yang; Chun-Hao Yang; Shi-Jun He; Jian-Ping Zuo (Science China Life Sciences, 2025)

Multi-objective evolutionary neural architecture search for network intrusion detection - Qiuzhen Lin; Zhihao Liu; Yeming Yang; Ka-Chun Wong; Yahui Lu; Jianqiang Li (Swarm and Evolutionary Computation, 2024)

Carbonate precipitation-derived CO2 outgassing offsets the mineral weathering sink in the orogenic regime of southwestern Taiwan: Insights from triple Sr isotopes - Hou-Chun Liu; Yun-Cian Lin; Yan-Hong Chen; Meng-Xuan Li; Chen-Feng You; Kuo-Fang Huang; Wei-Jen Huang; Hung-Chun Chao (Science of The Total Environment, 2024)

“Nano knife” for efficient piezocatalytic inactivation of amoeba spores and their intracellular bacteria: Synergetic effect between physical damage and chemical oxidation - Huinan Zhao; Jianyi Zheng; Wei Huang; Zhenzhen He; Fan Huang; Lin Zhang; Tao Zhong; Yadi Li; Dehua Xia; Longfei Shu; Chun He (Journal of Hazardous Materials, 2024)

Calcium regulates the physiological and molecular responses of Morus alba roots to cadmium stress - Ming-Jin Dai; Lu-Dan Zhang; Jing Li; Chun-Quan Zhu; Ling-Yu Song; He-Zi Huang; Chao-Qun Xu; Qing-Hua Li; Lin Chen; Chen-Kai Jiang; Hong-Ling Lu; Qiu-Tong Ling; et al. (Journal of Hazardous Materials, 2024)

The rational design of ratiometric probe based on fluorescence carbon dots and its PVA film platform for the detection of Hg2+: Tunable mechanism and the performance - Qiuyan Hu; Haiying Lin; Qingge Feng; Xianghua Wu; Lixin Huang; Yu Duan; Wenlu Lan; Zixuan Chen; Lianghong Li; Jiatong Lv; Jie He; Chun Lv; et al. (Journal of Environmental Chemical Engineering, 2024)

Experimental evaluation of bonded/unbonded prestressed precast concrete joints under repetitive loading scenarios: Seismic performance and retrofit intervention - Hao Fang; Hai-Rong Shi; Xiu-Hang Li; Chun-Lin Wang; Bin Zeng (Engineering Structures, 2024)

Source apportionment of PM2.5 episodes in the Taichung metropolitan area, Taiwan - Ming-Tung Chuang; Charles C.-K. Chou; Chuan-Yao Lin; Wei-Che Lin; Ja-Huai Lee; Meng-Hsuan Li; Wei-Nai Chen; Chih-Chung Chang; Chian-Yi Liu; Yi-Chun Chen (Atmospheric Research, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Hydrology controls sulfuric acid-mediated weathering in an orogenic regime of southwestern Taiwan - Hou-Chun Liu; Meng-Xuan Li; Chen-Feng You; Yan-Hong Chen; Kuo-Fang Huang; Chuan-Hsiung Chung; Guan-Wei Lin (Science of The Total Environment, 2024)

A surfactant-mediated dynamic protection strategy for 100% waterborne fabrication of durable superhydrophobic coatings - Rong-Gang Zhang; Rui Feng; Fang Wang; Hang-Lin Li; Ren-Yi Sun; Hui-Hui Gao; Chun-Bo Li; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2024)

Janus-Adhesive ionogels for wearable Real-Time monitoring and prevention of infantile meningitis - Xiao-Chun Yang; Xiao-Xue Wang; Chen-Yu Wang; Meng Yin; Ke Ma; Yan Li; Ke-Zheng Chen; Sheng-Lin Qiao (Chemical Engineering Journal, 2024)

A wearable exhaled breath condensate (EBC) collector with controllable condensation microfluidics and a branched hydrophilic film - Chun-Hao Chang; Ying-Hsuan Yu; Hsiu-Pen Lin; Ping-Hsien Tsou; Yaw-Kuen Li; Bor-Ran Li (Chemical Engineering Journal, 2024)

Efficient caproate production from lignocellulose via single-step electro-fermentation platform without organic electron donor - Yafei Zhang; Jianzheng Li; Xu Lian; Lin Li; Yang-chun Yong; Jia Meng (Bioresource Technology, 2024)

Formation Mechanism and Petroleum Geological Significance of (Ferro) Dolomite Veins from Fractured Reservoirs in Granite Buried Hills: Insights from Qiongdongnan Basin, South China Sea - Wei Duan; Cheng-Fei Luo; Lin Shi; Jin-Ding Chen; Chun-Feng Li (Journal of Marine Science and Engineering, 2024)
This study employs logging, petrology, and geochemistry to investigate the characteristics, origin, and hydrocarbon significance of fractures and (ferro) dolomite veins in a buried hill in the Qiongdongnan (QDN) Basin, South China Sea. We show that the study area is mainly characterized by three stages of fracturing with medium-high dipping angles. The orientation of the fractures is mainly NNW–SSE, consistent with the fault system strike formed by the Mesozoic–Cenozoic tectonic activity in the basin. (Ferro) dolomite veins in the fractures can be classified into three stages, all of which can be even observed in individual fractures. The first stage is the powdery crystal dolomite veins grown mainly on the fracture surface, which have the highest strontium isotope values, as well as high contents of the Mg element and extremely low contents of the Fe and Mn elements. The first-stage veins were formed in a relatively open oxidized environment, and the vein-forming fluids exhibit characteristics of mixing formation water and atmospheric freshwater within the fractures. The second stage, involving fine-crystal dolomite veins, was formed in a buried diagenetic environment where groundwater mixed with deep hydrothermal fluids, and contained the highest carbon isotope values, more Fe and Mn elements, and less Mg element than the first stage. The third stage of medium-crystal ankerite veins was formed in the latest stage, with the lowest strontium and oxygen isotope values. This was mainly a result of deep hydrothermal formation in which the rock-forming material formed from the interaction between the hydrothermal fluid and the iron-rich and aluminosilicate minerals in the surrounding granite of the fractures. We conclude that the multi-phase tectonic movements form a massive scale reticulated fracture inside the granite buried hill, which effectively improves the physical condition of the gas reservoirs. The gas reservoirs remain of high quality, despite the filling of the three stages of (ferro) dolomite veins.

Treatment of swine manure by hydrothermal carbonization: The influential effect and preliminary mechanism of surfactants - Zhen-tian Feng; Jiang-bo Xiong; Guo-feng Wang; Lin Li; Chun-fei Zhou; Chun-huo Zhou; Hua-jun Huang (Science of The Total Environment, 2024)

An innovative enhanced flotation approach of non-metallic components in waste printed circuit boards: Application of pyrolysis oil as self-generated collector - Chun-chen Nie; Qian-yun Sun; Xi-guang Li; Shuo Yang; Fei-fei Wang; Gang Hu; Si-qi Jiang; Xiang-nan Zhu; Lin Li; Xiao-fang You (Process Safety and Environmental Protection, 2024)

An unusual winter bloom of dinoflagellates with notable damage to kelp cultivation around Shandong peninsula, China - Hui-Xia Geng; Fan-Zhou Kong; Jin-Xiu Wang; Qing-Chun Zhang; Fang Li; Xin Hong; Min-Jie Song; Ziru Lian; Yu-Lin Cai; Ren-Cheng Yu (Marine Environmental Research, 2024)

MOF-derived carbon supporting tubular In2O3 for efficient photocatalytic degradation of antibiotics - Yilin Pan; Kaizhou Huang; Beijia Lin; Xiang Li; Chun Hu; Zhihong Chen; Peng Zhang (Journal of Environmental Chemical Engineering, 2024)

High efficiency in blue TADF OLED using favorable horizontal oriented host - Yi-Zhen Li; Hsuan-Chi Liang; Chia-Hsun Chen; Ching-Huang Chiu; Lian-Chun Huang; Yi-Ting Lee; Yi-Chung Dzeng; Chi Chen; Bo-Yen Lin; Jiun-Haw Lee; Tien-Lung Chiu; Man-kit Leung (Chemical Engineering Journal, 2024)

Composition modulation of electrocatalysts based on 3d transition metal towards high-performance Zn-air batteries - Ya-Fei Guo; Xu Liu; Shao-Jie Yang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Chun-Sheng Li; Jie Shu; Ting-Feng Yi (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Monoterpene-chalcone conjugates and diarylheptanoids isolated from the seeds of Alpinia katsumadai Hayata with cytotoxic activity - Hua-Lin You; Bo Zhou; Meng-Jia Guo; Xin-Man Zhao; Xiao-Long Li; Xiang-Chun Shen; Nen-Ling Zhang (Phytochemistry, 2024)

A down-regulated cytochrome P450 in Neoseiulus barkeri Hughes (Acari: Phytoseiidae) can dechlorinate and hydroxylate chlorpyrifos without producing chlorpyrifos-oxon - Shi-Jiang Yu; Li Wang; Li-Li Ding; Qi Pan; Si-Chen Li; Liu Liu; Lin Cong; Chun Ran (Journal of Hazardous Materials, 2024)

Rational design of robust Cu@Ag core-shell nanowires for wearable electronics applications - Yu-Chieh Kuo; Jiajun Fan; Lingqing Zong; Fandi Chen; Ziheng Feng; Chao Liu; Tao Wan; Zi Gu; Long Hu; Peiyuan Guan; Chun-Ho Lin; Mengyao Li; et al. (Chemical Engineering Journal, 2024)

A high-entropy strategy for stable structure of sodium ion batteries: From fundamentals to applications - Xu Liu; Xin-Yu Liu; Nan Zhang; Peng-Fei Wang; Zong-Lin Liu; Jun-Hong Zhang; Jie Shu; Yan Sun; Chun-Sheng Li; Ting-Feng Yi (Chemical Engineering Journal, 2024)

In-situ modification of nickel electrode by coupling the microbial corrosion and microbial reduction using Shewanella oneidensis for enhanced electrocatalysis - Jun-Lin Li; Jian-Li Mi; Zhuo-Lin Qing; Hao Hu; Si-Yuan Jia; Jun-Ying Liu; Yang-Chun Yong (Chemical Engineering Journal, 2024)

Effect of environmental exposome and influenza infection on febrile seizure in children over 22 years: a time series analysis - Xiaoting Jiang; Conglu Li; Qianying Yue; Yuchen Wei; Yawen Wang; Xiang Qian Lao; Guozhang Lin; Ka Chun Chong (International Journal of Biometeorology, 2024)
Febrile seizures are convulsions predominately occurring in young children. The effects of various exposomes, including influenza infection and external environmental factors, on febrile seizures have not been well-studied. In this study, we elucidated the relationships between ambient temperature, air pollutants, influenza infection, and febrile seizures using 22-year territory-wide hospitalization data in Hong Kong. The aggregated data were matched with the meteorological records and air pollutant concentrations. All-type and type-specific influenza-like illness positive (ILI+) rates were used as proxies for influenza activity. Distributed lag non-linear model in conjunction with the quasi-poisson generalized additive model was used to examine the associations of interest. According to the results, all-type influenza infections were significantly associated with an increased risk of hospital admissions for febrile seizures (cumulative adjusted relative risk [ARR] = 1.59 at 95th percentile vs. 0; 95% CI, 1.51–1.68). The effect of ILI + A/H3N2 on febrile seizure was more pronounced than other type-specific ILI + rates. A low mean ambient temperature was identified as a significant risk factor for febrile seizures (cumulative ARR = 1.50 at 5th percentile vs. median; 95% CI, 1.35–1.66), while the redox-weighted oxidant capacity and sulfur dioxide were not associated with febrile seizures. In conclusion, our study underscores that influenza infections and exposure to cold conditions were related to an increased risk of febrile seizures in children. Thus, we advocate for influenza vaccination before the onset of the cold season for children to mitigate the burden of febrile seizures.

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

Clean and efficient process for the recycling of all components from waste printed circuit boards: Pre-treatment, bio-metallurgy, and deep utilization - Chun-chen Nie; Xi-guang Li; Qian-yun Sun; Qiang Gao; Xiang-nan Zhu; Xian-jun Lyu; Lin Li; Xiao-fang You (Journal of Cleaner Production, 2024)

Fe0-mediated mixotrophic denitrification enhanced by carbon fiber for secondary effluent with low C/N ratio - Yi-Mei Cheng; Lin-Chun Jia; Gang Xue; Xian-Ying Li (Journal of Environmental Chemical Engineering, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Solar-driven adaptive radiative cooling coating with polymer carbon dots-enhanced photoluminescence for urban skin - Quan Gong; Ho Chun Wong; Jianheng Chen; Pei Li; Lin Lu (Chemical Engineering Journal, 2024)

HDAC inhibitors as a potential therapy for chemotherapy-induced neuropathic pain - Chalton Manengu; Chun-Hao Zhu; Guo-Dong Zhang; Miao-Miao Tian; Xiao-Bing Lan; Li-Jun Tao; Lin Ma; Yue Liu; Jian-Qiang Yu; Ning Liu (Inflammopharmacology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

TBC1D10B promotes tumor progression in colon cancer via PAK4‑mediated promotion of the PI3K/AKT/mTOR pathway - Xiao-Jv Chi; Yi-Bei Song; Haoran Zhang; Li-Qiang Wei; Yong Gao; Xue-Jing Miao; Shu-Ting Yang; Chun-Yu Lin; Dong Lan; Xiquan Zhang (Apoptosis, 2024)

A new phenylpropanoic acid congener from Zanthoxylum nitidum - Feng Qin; Li Luo; Yao Chen; Gang Wei; Chun-Ce Wei; Xiao-Hua Yang; Yi-Lin Fang; Heng-Shan Wang (Natural Product Research, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Phellintremulins A-C, antinociceptive sesquiterpenoids from the medicinal fungus Phellinus tremulae - Chun Tian; Li-Tang Sun; Tian Jin; Lin-Lin Yuan; Wei-Fang Xu; Hui-Xiang Yang; Tao Feng; Ji-Kai Liu (Phytochemistry, 2024)

The involvement of SigmaR1K142 degradation mediated by ERAD in neural senescence linked with CdCl2 exposure - Bo Qian; Ting-Yu Li; Zhao-Xuan Zheng; Han-Yu Zhang; Wen-Qi Xu; Su-Min Mo; Jia-Jia Cui; Wei-Jie Chen; Yu-Chun Lin; Zhong-Ning Lin (Journal of Hazardous Materials, 2024)

Sustainable and efficient deep eutectic solvents in recycling of spent lithium-ion batteries: Recent advances and perspectives - Wen-hao Gao; Chun-chen Nie; Lin Li; Shuai Yan; Wen-tao Zhou; Xiang-nan Zhu (Journal of Cleaner Production, 2024)

Soil organic carbon storage, microbial abundance and pore structure characteristics of macroaggregates across a soil-landscape sequence in a subtropical hilly watershed - Zheng Zhao; Xiao Feng; Chun Liu; Yue Han; Guogang Long; Shuotong Chen; Qingmei Lin; Jingwen Gong; Yi Shen; Ziyi Mao; Thammavongsa Sounilan; Xuhui Zhang; et al. (CATENA, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Evaluation of regional integration in urban agglomeration area from the perspective of urban symbiosis - Chun Li; Sijia Lin; Yiting Wang; Liding Chen (Sustainable Cities and Society, 2024)

Nitrogen fertilization modulates rice phyllosphere functional genes and pathogens through fungal communities - Wei-Feng Wu; Xin-Yuan Li; Song-Can Chen; Bing-Jie Jin; Chun-Yan Wu; Gang Li; Cheng-liang Sun; Yong-Guan Zhu; Xian-Yong Lin (Science of The Total Environment, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

A new acetophenone derivative from Rhododendron irroratum subsp. pogonostylum - Yong-Fu Lu; Si-Xuan Liu; Chun-Lin Guo; Si-Yang Dai; Yi-Hui Yang; Chang Li; Yue-Hu Pei (Phytochemistry Letters, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Dynamic analysis of lift-off operation of offshore wind turbine jacket foundation from the transportation barge - Mingsheng Chen; Guibo Yuan; Bin Li; Chun Bao Li; Mingjun Ouyang; Lin Li; Wei Shi; Zhaolong Han; Wei Zhang; Ziwen Chen (Ocean Engineering, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Activation of RXRα exerts cardioprotection through transcriptional upregulation of Ndufs4 in heart failure - Mingyan Shao; Lingru Li; Lin Ma; Chao Song; Weili Li; Yawen Zhang; Wenkun Cheng; Yun Chen; Ye Yang; Qian Wang; Chun Li; Qi Wang; et al. (Science Bulletin, 2024)

Decoding the genome of bloodsucking midge Forcipomyia taiwana (Diptera: Ceratopogonidae): Insights into odorant receptor expansion - Ming-Der Lin; Chia-Hsien Chuang; Chih-Hsin Kao; Shu-Hwa Chen; Szu-Chieh Wang; Ping-Heng Hsieh; Guan-Yu Chen; Chun-Chia Mao; Jeng-Yi Li; Mei-Yeh Jade Lu; Chung-Yen Lin (Insect Biochemistry and Molecular Biology, 2024)

Experimental and modeling study of ignition delay times of n-C5H12 and C3H6 under O2/CO2 atmospheres - Chao Peng; Chun Zou; Jiaxin Ren; Qianjin Lin; Wenxiang Xia; Lingfeng Dai; Jiacheng Liu; Wenyu Li (Fuel, 2024)

Hepatic injury and ileitis associated with gut microbiota dysbiosis in mice upon F–53B exposure - Shenpan Li; LuYin Wu; HuiXian Zeng; Jing Zhang; ShuangJian Qin; Li-Xia Liang; John Andersson; Wen-Jie Meng; Xing-Yu Chen; Qi-Zhen Wu; Li-Zi Lin; Wei-Chun Chou; et al. (Environmental Research, 2024)

LncRNA NR_030777 promotes mitophagy by targeting CDK1-related mitochondrial fission and ATG12 to attenuate paraquat-induced Parkinson's disease - Nengzhou Chen; Hong Hu; Jianping Tang; Fuli Zheng; Zhenkun Guo; Xinpei Lin; Michael Aschner; Wenya Shao; Guangxia Yu; Ping Cai; Wei-Chun Chou; Siying Wu; et al. (Environmental Pollution, 2024)

Short-term effects of exposure to cold spells on blood pressure among adults in Nanjing, China - Tian-Lin Li; Bei-Jing Cheng; Nan Jiang; Xing-Chen Meng; Chun Wang; Yang Huang; Ke Meng; Hui Li; Xin-Yi Zhu; Ran Liu (Air Quality, Atmosphere & Health, 2024)

The SMAC mimetic GDC-0152 is a direct ABCB1-ATPase activity modulator and BIRC5 expression suppressor in cancer cells - I-Li Lin; Yu-Ting Lin; Yung-Chieh Chang; Sree Karani Kondapuram; Kai-Hsuan Lin; Pin-Chen Chen; Chung-Ying Kuo; Mohane Selvaraj Coumar; Chun Hei Antonio Cheung (Toxicology and Applied Pharmacology, 2024)

Application of iron tailings in the coagulation of landfill leachate by bipolar membrane electrodialysis - Yanchao Jin; Guodong Wang; Zheng Li; Chun-Yan Lin; Li-Ping Li; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Journal of Cleaner Production, 2024)

Non-fitting functional representation for the equilibrium constant subject to reaction between H2S and CO2 - Chao-Wen Wang; Ji Li; Lie-Hui Zhang; Qun-Chao Ding; Guan-Hong Liu; Gao Li; Rui Jiang; Xiao-Long Peng; Lin-Sheng Wei; Hong-Ming Tang; Jian-Yi Liu; Chun-Sheng Jia (Fuel, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Lack of effects of eight-week left dorsolateral prefrontal theta burst stimulation on white matter macro/microstructure and connection in autism - Chun-Hung Yeh; Po-Chun Lin; Rung-Yu Tseng; Yi-Ping Chao; Chen-Te Wu; Tai-Li Chou; Rou-Shayn Chen; Susan Shur-Fen Gau; Hsing-Chang Ni; Hsiang-Yuan Lin (Brain Imaging and Behavior, 2024)

Identical metamorphic record in distinct petrochemical systems: Case study of microscopically interlayered garnet amphibolite and metapelite from the Danba dome, SW China - Zhen M.G. Li; Yi-Chao Chen; Fred Gaidies; Yan-Lin Zhao; Chun-Ming Wu (Lithos, 2024)

Physical drivers of Noctiluca scintillans (Dinophyceae) blooms outbreak in the northern Taiwan Strait: A numerical study - Zhonghao Lin; Peng Zhan; Jianping Li; Jun Sasaki; Zhongfeng Qiu; Chun Chen; Shuangyan Zou; Xiaotong Yang; Haifeng Gu (Harmful Algae, 2024)

A top-down and in situ strategy for intrinsic acicular nanostructure enhanced ultradurable superhydrophobic and anti-icing aramid fabric - Jin-Le Li; Fang Wang; Chun-Bo Li; Ren-Yi Sun; Mei-Lin Guo; Gang Wu; Fei Song; Yu-Zhong Wang (Chemical Engineering Journal, 2024)

Low temperature promotes the production and efflux of terpenoids in yeast - Lei Qin; Dongshi Ma; Guangyuan Lin; Wentao Sun; Chun Li (Bioresource Technology, 2024)

Application of proteomics in identifying crucial virulence factors shared by different Streptococcus iniae isolates for developing an effective subunit vaccine against S. iniae in tilapia - Chaio-Ping Chen; Shu-Chun Chuang; Kuan-Lun Su; Li-Kai Chen; Yi-Chen Lin; Yu-Jen Wu; Shang-Pin Liu; Shao-Wen Hung; Chung-Hwan Chen; Chung-Da Yang (Aquaculture, 2024)

The immune response of Caspase-3 gene in infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection of Litopenaeus vannamei - Cai-Yi Chen; Ning Yang; Chuanyu He; Yang Gao; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan (Aquaculture, 2024)

Neglected negative effect of carbon quantum dots (CQDs) entering the ocean on marine organisms living in different water layers - Xinyang Li; Ciara Chun Chen; Lin Wu; Jin Zhou; Yuxiong Huang; Xiaoshan Zhu (Marine Pollution Bulletin, 2024)

Acute septicemia and diagnostic evaluation of Aeromonas veronii infection in American bullfrogs (Aquarana catesbeiana) - Han Lin; Guilian Zeng; Yebing Yu; Hua Li; Kesong Chen; Zhendong Qin; Biao Jiang; Wei Li; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Potential causal links and mediation pathway between urban greenness and lung cancer mortality: Result from a large cohort (2009 to 2020) - Wenjing Wu; Gonghua Wu; Jing Wei; Wayne R Lawrence; Xinlei Deng; Yuqin Zhang; Shirui Chen; Ying Wang; Xiao Lin; Dan Chen; Xinling Ruan; Qiaoxuan Lin; et al. (Sustainable Cities and Society, 2024)

The dynamic mechanism of scientific and technological innovation in China’s marine biomedical industry - Xiu-Mei Fu; Yan-Xin Tan; Ying Liu; Ying-Hui Han; Qiao-Qiao Qi; Jing-Hang Li; Chun-Yu Lin (Frontiers in Marine Science, 2024)
As one of the important forces promoting the development of the marine economy, the marine biomedical industry (MBI) shows typical knowledge and technology-intensive characteristics. It is of great significance to explore the industrial innovation dynamic mechanism for breaking through the bottleneck of innovative development as well as achieving high-quality development. This paper constructed a system dynamics model for scientific and technological innovation (STI) in the MBI and then explored the dynamic mechanism of STI in the industry through simulation. The study found that, in the innovation environment subsystem, the two factors of the intellectual property protection intensity and the government’s scientific research funding input had the most significant positive driving effects on STI of the MBI; the promotion of government education funding input showed a significant strengthening trend over time, while the marine environmental regulation intensity had comparatively little effect on the level of STI. In the subsystem of innovation input, both innovation funding input and innovation personnel input were the direct driving forces for the improvement of the STI level. And enterprises played a dominant role in STI because the STI level of the MBI was more sensitive to the changes in enterprise innovation input. Compared with the individual factor input, the synergistic promotion effect of multiple factors is more significant. In addition, it was found that there was a low conversion rate of scientific research achievements in China’s MBI by analyzing the influence of various factors changing on technological output and economic output. Based on the research results, this paper puts forward corresponding policy suggestions in order to provide theoretical support and a practical basis for promoting the technological innovation level of China’s MBI as well as references for other countries.

Anthropogenic nitrogen pollution inferred by stable isotope records of crustose coralline algae - Aafaq Nazir; Chiao-Feng Lai; Shih-Wei Wang; Showe-Mei Lin; Hong-Chun Li; Ming-Tsung Chung; Pei-Ling Wang; Yung-Che Tseng; Jen-Chieh Shiao (Marine Pollution Bulletin, 2024)

CFD- and BPNN- based investigation and prediction of air pollutant dispersion in urban environment - Xisheng Lin; Yunfei Fu; Daniel Z. Peng; Chun-Ho Liu; Mengyuan Chu; Zengshun Chen; Fan Yang; Tim K.T. Tse; Cruz Y. Li; Xinxin Feng (Sustainable Cities and Society, 2024)

Wide-swath and high-resolution whisk-broom imaging and on-orbit performance of SDGSAT-1 thermal infrared spectrometer - Zhuoyue Hu; Xiaoyan Li; Liyuan Li; Xiaofeng Su; Lin Yang; Yong Zhang; Xingjian Hu; Chun Lin; Yujun Tang; Jian Hao; Xiaojin Sun; Fansheng Chen (Remote Sensing of Environment, 2024)

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

The apple lipoxygenase MdLOX3 positively regulates zinc tolerance - Guo-Lin Chen; Da-Ru Wang; Xin Liu; Xun Wang; Hao-Feng Liu; Chun-Ling Zhang; Zhen-Lu Zhang; Lin-Guang Li; Chun-Xiang You (Journal of Hazardous Materials, 2024)

Investigation of bacterial diversity from hybrid water sources to multiple terminal sites on an isolated island in the south China sea - Xiao Chen; Xiao-Nan Wu; Jing-Chun Feng; Yi Wang; Shu-Jun Yang; Jie Kong; Ying-Li Zhou; Jun-Lin Hu; Ke Ding; Si Zhang (Journal of Cleaner Production, 2024)

Bacterial, short-chain fatty acid and gas profiles of partially hydrolyzed guar gum in vitro fermentation by human fecal microbiota - Xiong-E Pi; Hao Fu; Xiao-Xia Yang; Zai-Chun Yu; Wei-Lin Teng; Yinjun Zhang; Xue-Wei Ye; Hui Hui Quan; Li-Zhi Lu; Wei Liu (Food Chemistry, 2024)

Interaction among local flows, UHI, coastal winds, and complex terrain: Effect on urban-scale temperature and building energy consumption during heatwaves - Ruiqing Du; Chun-Ho Liu; Xianxiang Li; Chuan-Yao Lin (Energy and Buildings, 2024)

Micro-scale urbanization-based risk factors for dengue epidemics - Pei-Sheng Lin; Wei-Liang Liu; Chaur-Dong Chen; Tzai-Hung Wen; Chun-Hong Chen; Li-Wei Chen; Yi-Hung Kung (International Journal of Biometeorology, 2024)

Eco-friendly approach for enhancing the floatability of non-metallic components in waste printed circuit boards: Adding gutter oil during dry grinding - Chun-chen Nie; Si-qi Jiang; Xi-guang Li; Xiao-ru Wang; Zhi-hao Li; Xiang-nan Zhu; Xian-jun Lyu; Xiao-fang You; Lin Li (Waste Management, 2023)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Clinical comprehensive evaluation of direct oral anticoagulants for patients with atrial fibrillation in China - Chi Zhang; Zhi-Chun Gu; Er-Li Ma; Bing-Long Liu; Mang-Mang Pan; Jia Wang; Xin Wang; Bin Wu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2023)

Joint full waveform inversion of multiple instantaneous attributes - Kai Zhang; Yi-peng Xu; Fei Xie; Cheng-hong Zhu; Zhen-chun Li; Zi-Lin He (Applied Geophysics, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Preparation of hypercrosslinked porous polymer with manifold functional groups for sensitive determination of phenylurea herbicides in beverages and celtuce samples - Linna Guo; Miao Tian; Zhi Li; Qianqian Wang; Qiuhua Wu; Lin Hao; Chun Wang (Food Chemistry, 2023)

Flooding dominates soil microbial carbon and phosphorus limitations in Poyang Lake wetland, China - Xingyun Huang; Yaxuan Li; Huiyin Lin; Xiuting Wen; Jie Liu; Zhifen Yuan; Chun Fu; Bofu Zheng; Leiqiang Gong; Huiying Zhan; Yu Ni; Yang Hu; et al. (CATENA, 2023)

The NOx-O3 photochemical reactive air pollutant dispersion around an isolated building—the role of turbulence model and building aspect ratio - Yunfei Fu; Xisheng Lin; Lu Li; Mengyuan Chu; Chun-Ho Liu; Zengshun Chen; Cruz Y. Li; K.T. Tse (Building and Environment, 2023)

Sesquiterpene coumarins from Ferula sinkiangensis and their anti-pancreatic cancer effects - Jia-Lin Wang; Chun-Yan Sang; Jun Wang; Pei-Lin Li; Tian Chai; Mohammad Reza Naghavi; Ya-Min Zhao; Jun-Li Yang (Phytochemistry, 2023)

Per- and polyfluoroalkyl substances in ambient fine particulate matter in the Pearl River Delta, China: Levels, distribution and health implications - Lu-Sheng Liu; Yu-Ting Guo; Qi-Zhen Wu; Mohammed Zeeshan; Shuang-Jian Qin; Hui-Xian Zeng; Li-Zi Lin; Wei-Chun Chou; Yun-Jiang Yu; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Pollution, 2023)

Association of Ferroptosis with Severity and Outcomes in Acute Ischemic Stroke Patients Undergoing Endovascular Thrombectomy: A Case-control Study - Shin-Joe Yeh; Chih-Hao Chen; Yen-Heng Lin; Li-Kai Tsai; Chung-Wei Lee; Sung-Chun Tang; Jiann-Shing Jeng (Molecular Neurobiology, 2023)

Association of air pollutants and meteorological factors with tuberculosis: a national multicenter ecological study in China - Qian Wang; Yan-lin Li; Ya-ling Yin; Bin Hu; Chong-chong Yu; Zhen-de Wang; Yu-hong Li; Chun-jie Xu; Yong-bin Wang (International Journal of Biometeorology, 2023)

USP14 Regulates ATF2/PIK3CD Axis to Promote Microvascular Endothelial Cell Proliferation, Migration, and Angiogenesis in Diabetic Retinopathy - Fu-Tao He; Xiao-Lin Fu; Mo-Han Li; Chun-Yan Fu; Jian-Zhi Chen (Biochemical Genetics, 2023)

Three new compounds with their anti-glioma effects from the roots of Arnebia guttata Bunge - Yu-Mei Yan; Lin-Jun Zou; Min-Hui Li; Zhao-Cui Sun; Min Zhang; Xu-Dong Xu; Chun-Hong Zhang (Natural Product Research, 2023)

Short-term effects of cold spells on hematocrit among adults in Nanjing, China: A distributed-lagged effect analysis - Bei-Jing Cheng; Tian-Lin Li; Hui Li; Ke Meng; Xing-Chen Meng; Jia Wang; Chun Wang; Lin-Sheng Yang; Xin-Yi Zhu; Ran Liu (Science of The Total Environment, 2023)

Study of the influence under different operating conditions on the performance of hydrogen fuel cell system for a bus - Yan Hong Yang; Qiao Lin; Chun Feng Zhang; Gao Qiang Li (Process Safety and Environmental Protection, 2023)

Research progress in steroidal saponins from the genus Polygonatum: Chemical components, biosynthetic pathways and pharmacological effects - Chunfang Xu; Bohou Xia; Zhimin Zhang; Yan Lin; Chun Li; Limei Lin (Phytochemistry, 2023)

Degradation of indole via a two-component indole oxygenase system from Enterococcus hirae GDIAS-5 - Jun-Jin Deng; Jing-Yi Hu; Xue-ying Han; Yang Li; Xiao-Chun Luo; Zhi-Lin Wang; Jia-Zhou Li (Journal of Hazardous Materials, 2023)

Over-expression of miR-3584-5p Represses Nav1.8 Channel Aggravating Neuropathic Pain caused by Chronic Constriction Injury - Ran Yang; Qian-qian Wang; Yuan Feng; Xue-hao Li; Gui-xia Li; Feng-lin She; Xi-jin Zhu; Chun-li Li (Molecular Neurobiology, 2023)

Driving forces and their interactions of soil erosion in soil and water conservation regionalization at the county scale with a high cultivation rate - Bang-lin Luo; Jiang-wen Li; Chun-ming Gong; Shou-qin Zhong; Chao-fu Wei (Journal of Mountain Science, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Treatment of diluted palm oil mill effluent (POME) synchronous with electricity production in a persulfate oxidant-promoted photocatalytic fuel cell - Chun-Ting Joyee Yap; Sze-Mun Lam; Jin-Chung Sin; Honghu Zeng; Haixiang Li; Liangliang Huang; Hua Lin (Environmental Science and Pollution Research, 2023)

Dihydromyricetin attenuates cisplatin-induced acute kidney injury by reducing oxidative stress, inflammation and ferroptosis - Zheming Xu; Minjing Zhang; Wenwen Wang; Suhan Zhou; Minghua Yu; Xingyu Qiu; Shan Jiang; Xiaohua Wang; Chun Tang; Shuijie Li; Chih-Hong Wang; Runzhi Zhu; et al. (Toxicology and Applied Pharmacology, 2023)

Genomic analysis of Marinomonas algicola SM1966T reveals its role in marine sulfur cycling - Min Zhang; Xiao-Di Wang; Yue Lin; Shu-Yan Wang; Shan Zhang; Jin Cheng; Mei-Ling Sun; Peng Wang; Hui-Hui Fu; Chun-Yang Li; Nan Zhang (Marine Genomics, 2023)

Decoupling analysis to assess the impact of land use patterns on carbon emissions: A case study in the Yellow River Delta efficient eco-economic zone, China - Qian Wang; Chuan-hao Yang; Ma-li Wang; Lin Zhao; Yu-chen Zhao; Qi-peng Zhang; Chun-yan Zhang (Journal of Cleaner Production, 2023)

Dating seafloor spreading of the southwest sub-basin in the South China Sea - Ning Qiu; Zhen Sun; Jian Lin; Chun-Feng Li; Xing Xu (Gondwana Research, 2023)

Extensional structures and Cenozoic magmatism in the northwestern South China Sea - Jinwei Gao; Shiguo Wu; Thomas Lüdmann; Chun-Feng Li; Lin Li; Yintao Lu; Zhili Yang; Liyan Tian; Yongpeng Qin; Taoran Song (Gondwana Research, 2023)

Teleost skin microbiome: An intimate interplay between the environment and the host immunity - Liang-Chun Wang; Li-Hsuan Chen; Yu-Che Chiu; Chung-Yi Liou; Han-Chung Chen; Chia-Yun Lu; Jian-Lin Chen (Fish & Shellfish Immunology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

A new sesquiterpene synthase catalyzing the formation of (R)-β-bisabolene from medicinal plant Colquhounia coccinea var. mollis and its anti-adipogenic and antibacterial activities - De-Sen Li; Lin-Lin Shi; Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Yue-Gui Chen; Yan Liu; Sheng-Hong Li (Phytochemistry, 2023)

Study of infectious hypodermal and hematopoietic necrosis virus (IHHNV) infection in different organs of Penaeus vannamei - Zi-Hao Hou; Yang Gao; Jing-Jing Wang; Cai-Yi Chen; Lin-Rui Chang; Ting Li; Ling-Jun Si; Fan Li; Dong-Chun Yan (Journal of Invertebrate Pathology, 2023)

Axial compressive behaviour of concrete encased extended I-shaped steel composite stub columns with less reinforcement - Chuan-Hao Li; Xue-Chun Liu; Ai-Lin Zhang; Xuesen Chen; Jing Zhang; Zhaoqi Li (Engineering Structures, 2023)

Management‐induced changes in soil organic carbon and related crop yield dynamics in China's cropland - Bai‐Jian Lin; Ruo‐Chen Li; Ke‐Chun Liu; Olatunde Pelumi Oladele; Zhi‐Yu Xu; Rattan Lal; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2023)
Enhancing soil organic carbon (SOC) sequestration and food supply are vital for human survival when facing climate change. Site‐specific best management practices (BMPs) are being promoted for adoption globally as solutions. However, how SOC and crop yield are related to each other in responding to BMPs remains unknown. Here, path analysis based on meta‐analysis and machine learning was conducted to identify the effects and potential mechanisms of how the relationship between SOC and crop yield responds to site‐specific BMPs in China. The results showed that BMPs could significantly enhance SOC and maintain or increase crop yield. The maximum benefits in SOC (30.6%) and crop yield (79.8%) occurred in mineral fertilizer combined with organic inputs (MOF). Specifically, the optimal SOC and crop yield would be achieved when the areas were arid, soil pH was ≥7.3, initial SOC content was ≤10 g kg −1 , duration was >10 years, and the nitrogen (N) input level was 100–200 kg ha −1 . Further analysis revealed that the original SOC level and crop yield change showed an inverted V‐shaped structure. The association between the changes in SOC and crop yield might be linked to the positive role of the nutrient‐mediated effect. The results generally suggested that improving the SOC can strongly support better crop performance. Limitations in increasing crop yield still exist due to low original SOC level, and in regions where the excessive N inputs, inappropriate tillage or organic input is inadequate and could be diminished by optimizing BMPs in harmony with site‐specific conditions.

U-shaped association between low-density lipoprotein cholesterol levels and risk of all-cause mortality mediated by post-stroke infection in acute ischemic stroke - Zi-Mo Chen; Hong-Qiu Gu; Jing-Lin Mo; Kai-Xuan Yang; Ying-Yu Jiang; Xin Yang; Chun-Juan Wang; Jie Xu; Xia Meng; Yong Jiang; Hao Li; Li-Ping Liu; et al. (Science Bulletin, 2023)

Cyano-functionalized ionic porous polymer: A novel adsorbent for effectively enriching trace estrogens in water and milk - Zixuan Cai; Xin Zhou; Yushi Yang; Jie Li; Weihua Liu; Qianqian Wang; Lin Hao; Zhi Wang; Yusuke Yamauchi; Jungmok You; Shuaihua Zhang; Qiuhua Wu; et al. (Chemical Engineering Journal, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Ciprofloxacin degradation performances and mechanisms by the heterogeneous electro-Fenton with flocculated fermentation biochar - Yanchao Jin; Peiwen Huang; Xiongjian Chen; Li-Ping Li; Chun-Yan Lin; Xiao Chen; Rui Ding; Jianxi Liu; Riyao Chen (Environmental Pollution, 2023)

Salinibacterium sedimenticola sp. nov., Isolated from Tidal Flat Sediment - Chun-Yan Lu; Lei Dong; Shuai Li; Wen-Hui Lian; Zhi-Liang Lin; Zhuo-Huan Zheng; Lei Gao; Bao-Zhu Fang; Wen-Jun Li (Current Microbiology, 2023)

Punctiform Breakup and Initial Oceanization in the Central Red Sea Rift - Ya-Di Sang; Bakhit M. T. Adam; Chun-Feng Li; Liang Huang; Yong-Lin Wen; Jia-Ling Zhang; Yu-Tao Liu (Journal of Marine Science and Engineering, 2023)
The Central Red Sea Rift is a natural laboratory to study the transition from rifting to spreading. Based on new reflection seismic profiles and gravity modeling, we examined the crustal structure, tectonic evolution, breakup mechanism, and future evolution of the Central Red Sea Rift. Along this rift axis, the breakup of continental lithosphere is discontinuous and the oceanic crust is limited to the axial deeps. The punctiform breakup and formation of deeps is assisted by mantle upwelling and topographic uplift, but the nucleation is directly controlled by the normal-fault system. The discontinuities spaced between axial deeps within the relatively continuous central troughs are presently axial domes or highs and will evolve into new deeps with tectonic subsidence. Isolated deeps will grow and connect with each other to become a continuous central trough, before transitioning into a unified spreading center.

Rab7a-mTORC1 signaling-mediated cholesterol trafficking from the lysosome to mitochondria ameliorates hepatic lipotoxicity induced by aflatoxin B1 exposure - Jin-Xian Lin; Chi-Yu Xu; Xin-Mou Wu; Lin Che; Ting-Yu Li; Su-Min Mo; Dong-Bei Guo; Zhong-Ning Lin; Yu-Chun Lin (Chemosphere, 2023)

Detection and quantification of Klebsiella pneumoniae in American bullfrog (Rana catesbeiana) by Taqman MGB probe real-time fluorescence quantitative PCR - Han Lin; Jingyang Sun; Jie Ma; Zhendong Qin; Biao Jiang; Wei Li; Qing Wang; Youlu Su; Li Lin; Chun Liu (Aquaculture, 2023)

Lactobacillus plantarum isolated from kefir enhances immune responses and survival of white shrimp (Penaeus vannamei) challenged with Vibrio alginolyticus - Kuo-Chun Tseng; Huai-Ting Huang; Shu-Ning Huang; Fang-Yi Yang; Wen-Hsiung Li; Fan-Hua Nan; Yu-Ju Lin (Fish & Shellfish Immunology, 2023)

Polystyrene microplastics arrest skeletal growth in puberty through accelerating osteoblast senescence - Chun Pan; Yin Wu; Sihan Hu; Ke Li; Xiangyu Liu; Yu Shi; Wenzheng Lin; Xinglong Wang; Yujie Shi; Zhuobin Xu; Huihui Wang; Hao Chen (Environmental Pollution, 2023)

Lipopolysaccharide-induced endotoxaemia during adolescence promotes stress vulnerability in adult mice via deregulation of nuclear factor erythroid 2-related factor 2 in the medial prefrontal cortex - Yan-chen Chen; Yan-hua Huang; Li Song; Xiao-han Tong; Jun-feng Li; Song Lin; Xi Chen; Ji-chun Zhang; Zi-li Zhang; Qi-yi Zeng (Psychopharmacology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Hyperbaric Oxygen Therapy Attenuated the Motor Coordination and Cognitive Impairment of Polyglutamine Spinocerebellar Ataxia SCA17 Mice - Meng-Ke Chiang; Ta-Chun Lin; Keng-Hsuan Lin; Ya-Chin Chang; Hsiu Mei Hsieh-Li; Dar-Ming Lai (The Cerebellum, 2023)

The impact of temperature and precipitation on all-infectious-, bacterial-, and viral-diarrheal disease in Taiwan - Gerry Andhikaputra; Amir Sapkota; Yu-Kai Lin; Ta-Chien Chan; Chuansi Gao; Li-Wen Deng; Yu-Chun Wang (Science of The Total Environment, 2023)

ZIF-8 sacrificial-templated hollow COF architectures enabled highly efficient enrichment, determination and regulation of food hazards from infant formulas - Lu Yang; Lin-Qing Nie; Jing Wang; Chun-Yang Li; Jin Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2023)

Phenyl-imidazole based and nitrogen rich hyper-crosslinked polymer for sensitive determination of aflatoxins - Mingming Xu; Zhijun Zhou; Lin Hao; Zhi Li; Jie Li; Qianqian Wang; Weihua Liu; Chun Wang; Zhi Wang; Qiuhua Wu (Food Chemistry, 2023)

Preparation of magnetic hyper-crosslinked polymer for high efficient preconcentration of four aflatoxins in rice and sorghum samples - Jie Li; Bin Zhao; Lin Hao; Weihua Liu; Chun Wang; Zhi Wang; Qiuhua Wu (Food Chemistry, 2023)

Spinal P2X4 Receptors Involved in Visceral Hypersensitivity of Neonatal Maternal Separation Rats - Ying Tang; Li Chen; Bin Liu; Pei Sun; Zhong Chen; Yang Huang; Chen Ai-qin; Yu Chen; Chun Lin (Purinergic Signalling, 2023)

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Identification of SNPs and candidate genes associated with early growth in orange-spotted grouper (Epinephelus coioides) by a genome-wide association study - Chun Hui Ai; Zong Xian Zhu; Dan Dan Huang; Gan Yang; Tong De Liu; Ying Bai; Xue Ying Liang; Ying Ying Xiong; Yi Long Lin; Hao Ran Lin; Shui Sheng Li; Jun Hong Xia (Aquaculture, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Sonocatalytic removal of tetracycline in the presence of S-scheme Cu2O/BiFeO3 heterojunction: Operating parameters, mechanisms, degradation pathways and toxicological evaluation - Xin Wang; Xue-Song He; Chun-Yu Li; Shi-Lin Liu; Wen Lu; Zheng Xiang; Yang Wang (Journal of Water Process Engineering, 2023)

Studies on micromorphology and permeability of hydrate-bearing porous media - Gang Li; Yi-Fan Weng; Xiao-Sen Li; Ze-Lin Xu; Qiu-Nan Lv; Chun-Gang Xu (Fuel, 2023)

Experimental study on a dry-assembled precast concrete frame with buckling-restrained braces - Yuan Qing; Xiuhang Li; Chun-Lin Wang; Bin Zeng; Shaoping Meng (Engineering Structures, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Chemical constituents from Lagopsis supina and their chemotaxonomic significance - Kai Wang; Stanislas Nsanzamahoro; Pei-Lin Li; Tian Chai; Cheng-Bo Wang; Chun-Yan Sang; Jun Wang; Jun-Li Yang (Biochemical Systematics and Ecology, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Seismic Multiple Attenuation in the Continent–Ocean Transition Zone of the Northern South China Sea - Nan Chen; Chun-Feng Li; Yong-Lin Wen; Peng Wang; Xiu-Lian Zhao; Xiao-Li Wan (Journal of Marine Science and Engineering, 2023)
In this study, we process four new multichannel reflection seismic profiles acquired in 2015 and 2016 in the continent–ocean transition zone (COT) of the northern South China Sea (SCS). We apply a multi-domain, progressive, and seabed-controlled denoising technique and obtain a good denoising effect. Combining velocity analysis in the multi-round time domain and forward modeling, we analyze the types and characteristics of multiples in the study area and formulate an effective demultiple technique to attenuate strong seabed multiples, diffracted multiples from rough seafloor, and other multiples from deep reflectors. The processing results show that the sea surface-related multiple elimination technique predicts the sea surface-related multiples accurately by data convolution, and has a good effect in attenuating seabed multiples. Diffracted multiple attenuation method extracts high-frequency and high-energy diffracted multiples, and suppresses multiples by the energy ratios of multiples to primary events. To attenuate deep multiples, we select predictive deconvolution to attenuate periodic deep multiples after many trials and detailed analysis. The combination of these different techniques in sequence proves to be quite effective in attenuating different seismic multiples in the COT. The imaged crustal structures near the COT often show strong magmatism and/or basement uplifting. The faulted and thinned continental crust adjacent to the COT corresponds to the lowest free-air gravity anomalies. Gravity anomalies often increase from the COT to the oceanic crust. An exception is to the northeast of the SCS, where the relatively wide COT shows very high gravity anomalies, likely induced by mantle upwelling and serpentinization.

The construction of high efficient visible-light-driven 3D porous g-C3N4/Fe3O4 photocatalyst: A new photo-induced bacterial inactivation material enhanced by cascade photo-Fenton reaction - Ze-Yu Liu; Wen-Qian Huang; Chuan-Qing Huang; Zhao-Zhen Liu; Xiao-Yue Tang; Wei-Chang Chen; Zheng-Zheng Tang; Yu-Xing Huang; Shuo-Chun Zheng; Lin Lin; Changzhu Li; Yong Ye (Chemosphere, 2023)

A pectic polysaccharide from fresh okra (Abelmoschus esculentus L.) beneficially ameliorates CCl4-induced acute liver injury in mice by antioxidation, inhibition of inflammation and modulation of gut microbiota - Jing-Kun Yan; Chun Wang; Ting-Ting Chen; Jie Zhu; Xu Chen; Longqing Li; Xiaozhen Liu; Henan Zhang; Lin Li (Food and Chemical Toxicology, 2023)

Andrographolide ameliorates hepatic steatosis by suppressing FATP2-mediated fatty acid uptake in mice with nonalcoholic fatty liver disease - Li-Sha Ran; Ya-Zeng Wu; Yi-Wen Gan; Hong-Lian Wang; Li-Juan Wu; Chun-Mei Zheng; Yao Ming; Ran Xiong; Yong-Lin Li; Shi-Hang Lei; Xue Wang; Xiao-Qing Lao; et al. (Journal of Natural Medicines, 2023)
Excessive intrahepatocellular lipid accumulation or steatosis is caused by abnormal lipid metabolism and a common character of nonalcoholic fatty liver disease (NAFLD), which may progress into cirrhosis and hepatocellular cancer. Andrographolide (Andro) is the primary active ingredient extracted from Andrographis paniculata , showing a protective role against dietary steatosis with the mechanism not fully understood. In this study, we showed that administration of Andro (50, 100, and 200 mg/kg/day for 8 weeks, respectively) attenuated obesity and metabolic syndrome in high-fat diet (HFD)-fed mice with improved glucose tolerance, insulin sensitivity, and reduced hyperinsulinemia, hyperglycemia, and hyperlipidemia. HFD-fed mice presented hepatic steatosis, which was significantly prevented by Andro. In vitro, Andro decreased the intracellular lipid droplets in oleic acid-treated LO2 cells. The selected RT-PCR array revealed a robust expression suppression of the fatty acid transport proteins (FATPs) by Andro treatment. Most importantly, we found that Andro consistently reduced the expression of FATP2 in both the oleic acid-treated LO2 cells and liver tissues of HFD-fed mice. Overexpression of FATP2 abolished the lipid-lowering effect of Andro in oleic acid-treated LO2 cells. Andro treatment also reduced the fatty acid uptake in oleic acid-treated LO2 cells, which was blunted by FATP2 overexpression. Collectively, our findings reveal a novel mechanism underlying the anti-steatosis effect of Andro by suppressing FATP2-mediated fatty acid uptake, suggesting the potential therapeutic application of Andro in the treatment of NAFLD. Graphical abstract

Dynamic Analysis and Extreme Response Evaluation of Lifting Operation of the Offshore Wind Turbine Jacket Foundation Using a Floating Crane Vessel - Mingsheng Chen; Guibo Yuan; Chun Bao Li; Xianxiong Zhang; Lin Li (Journal of Marine Science and Engineering, 2022)
The jacket is the most widely-used fixed foundation for offshore wind turbines due to its superior strength and low installation cost in relatively deep waters. Floating crane vessels are commonly used to install jacket foundations. However, the dynamic coupling between the jacket and the floating vessel might generate complex dynamic responses under wave action. The complexity of the multi-body system requires comprehensive time-domain simulations and statistical analysis to obtain reliable results, especially for the evaluation of the operational safety of offshore lift installations of a jacket foundation. In this context, this study performs numerical simulations and statistical analyses to predict the extreme responses and the preliminary allowable sea states for guiding the lowering operation of a jacket using a floating crane vessel. First, ANSYS-AQWA is used to obtain the hydrodynamic coefficients of the vessel in the frequency domain. A nonstationary time-domain simulation of jacket lowering with winches is performed to identify several preliminary critical vertical positions of the jacket from the time series in an irregular wave. The extreme responses of a target probability are evaluated by the extreme distribution model after a large number of steady-state time-domain simulations of the critical vertical positions in irregular waves. The most critical vertical position is determined from three preliminary critical vertical positions by comparing the extreme responses. Eigenvalue analysis and spectrum analysis of the most critical vertical position of the jacket are carried out to find the natural periods of the system and the dynamic coupling characteristics between different components. The influence of wave direction, significant wave height, and spectrum peak period on the dynamic responses are also analyzed in the most critical vertical position. Furthermore, the optimal wave direction is determined as the head sea. Preliminary allowable sea states are derived by comparing the calculated dynamic amplification coefficient with the defined operational criteria.

Transplantation of Nasal Olfactory Mucosa Mesenchymal Stem Cells Benefits Alzheimer’s Disease - Chun-Gu Hong; Meng-Lu Chen; Ran Duan; Xin Wang; Zhi-Lin Pang; Li-Te Ge; Ming Lu; Hui Xie; Zheng-Zhao Liu (Molecular Neurobiology, 2022)

AIoT-Based Ergometer for Physical Training in Frail Elderly with Cognitive Decline: A Pilot Randomized Control Trial - Chih-Chun Lin; Li-Chieh Kuo; Yu-Sheng Lin; Chia-Ming Chang; Fang Wen Hu; Yi-Jing Chen; Chun-Tse Lin; Fong-Chin Su (Journal of Medical and Biological Engineering, 2022)
Purpose Reduced physical activity is reported in the elderly, especially in institutional residents. Institutionalized older adults exhibit a high prevalence of frailty. In this work, we developed an artificial intelligence of things (AIoT)-based feedback assistive strengthening ergometer (AIFASE), for the physical strengthening of the elderly with intelligent assistance. Methods We conducted a 12-week intervention in a long-term care facility. In total, 16 participants (84.38 ± 6.0 years; 4 males and 12 females) were recruited with 1:1 randomization of exercise to control groups. The muscle strength of the lower extremities, timed up and go test (TUG), and Short-form Physical Performance Battery (SPPB) of the participants were measured. The AIFASE system allows the clinical staff to record the personal physical performance of the elderly and generates personalized exercise prescriptions accordingly. AIFASE also displays the current usage status of all ergometers and the users’ physiological conditions. The algorithms were developed to generate warning alerts when the training workload was too large by personal physiological detection. AIFASE automatically customized the exercise prescription according to the user’s exercise performance. Results After a 12-week AIFASE intervention, the intervention group exhibited significant improvements in the strength of the hip flexor, Semi-Tandem Stand, and Tandem Stand. Conclusion In this study, we developed an AIoT ergometer that delivered customized physical training prescriptions to improve the physical performance of long-term care facility residents. We believe that the application of AIFASE will help improve the quality of institutional care.

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Comparison of ticagrelor and clopidogrel on platelet function and prognosis in unstable angina - Chun Li; Ming Liu; Weixiang Chen; Tingbo Jiang; Lin Ling (European Journal of Clinical Pharmacology, 2022)
Purpose This study aims to compare the effects of ticagrelor and clopidogrel on platelet function, cardiovascular prognosis, and bleeding in patients with unstable angina pectoris. Methods Patients with unstable angina pectoris undergoing percutaneous coronary intervention (PCI) were enrolled (January 2018–December 2019). In total, 212 patients were treated with ticagrelor (90 mg twice daily) and 210 patients were treated with clopidogrel (75 mg once daily). Thromboelastography and light transmission aggregometry were used to measure the platelet aggregation rate (PAR). High-sensitivity troponin T (hs-TnT), pro-brain natriuretic peptide (NT-proBNP), high-sensitivity C-reactive protein (CRP), and heart-type fatty acid–binding protein (h-FABP) were measured to assess myocardial injury after PCI. Cardiovascular prognosis and bleeding events were evaluated in hospital and 12 months after discharge. Results The PAR was significantly slower with ticagrelor ( P < 0.001). hs-TnT, NT-proBNP, CRP, and h-FABP increased after compared with before PCI in both groups ( P < 0.05). hs-TnT ( P < 0.001) and h-FABP ( P < 0.001) increased more significantly with clopidogrel. The in-hospital and 12-month major adverse cardiovascular event (MACE) rates were not significantly different between the two groups. The in-hospital total bleeding event rate was higher with ticagrelor ( P < 0.05). Minor bleeding and total bleeding were more frequent at the 12-month follow-up in the ticagrelor group ( P < 0.05). Conclusion Ticagrelor was more effective in suppressing the PAR than clopidogrel and reduced PCI-induced myocardial injury in patients with unstable angina pectoris. However, it increased in-hospital and 12-month bleeding events and had no benefit on in-hospital and 12-month MACEs.

First report of leaf blight on Panax notoginseng caused by Pestalotiopsis trachycarpicola in China - Cheng Zhong Lan; Xiong Lin; Yu Li Dai; Lin Gan; Xiao Fei Liu; Hong Chun Ruan; Xiu Juan Yang (Journal of Plant Pathology, 2022)

Release of Endogenous Brain-derived Neurotrophic Factor into the Lateral Entorhinal Cortex from the Paraventricular Thalamus Ameliorates Social Memory Deficits in a Mouse Model of Alzheimer’s Disease - Yun-Long Xu; Lin Zhu; Zi-Jun Chen; Xiao-Fei Deng; Pei-Dong Liu; Shan Li; Bing-Chun Lin; Chuan-Zhong Yang; Wei Xu; Kui-Kui Zhou; Ying-Jie Zhu (Neuroscience Bulletin, 2022)

Comprehensive comparison of the prognostic value of systemic inflammation biomarkers for cancer cachexia: a multicenter prospective study - Hailun Xie; Guotian Ruan; Lishuang Wei; Heyang Zhang; Yizhong Ge; Qi Zhang; Shiqi Lin; Mengmeng Song; Xi Zhang; Xiaoyue Liu; Ming Yang; Meng Tang; et al. (Inflammation Research, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Two new clerodane diterpenoids and a new pyran-2-one derivative with anti-neuroinflammatory activities from Croton crassifolius - Zhi-Peng Ling; Qing Tang; Can-Jie Li; Jin-Lin Tan; Hai-Yue Zhao; Yi-Kun Hao; Zhao-Chun Zhan; Zhong-Nan Wu; Yu-Bo Zhang; Qing Zheng; Guo-Cai Wang (Journal of Natural Medicines, 2022)

Validity Analysis of the Morphological Identification of Three Highly Morphologically Similar Species Belonging to the Genus Niviventer (Rodentia: Muridae) - Yao-Yao Li; Hao-Tian Li; Jia-Wei Hao; Chen-Yi Zhang; Guan-Ze Liu; Xing-Han Lin; Xiao-Qing Sun; Guo-Chen Zang; Yu-Chun Li (Journal of Mammalian Evolution, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Identification of Key Pathways and Genes in SARS-CoV-2 Infecting Human Intestines by Bioinformatics Analysis - Ji-Chun Chen; Tian-Ao Xie; Zhen-Zong Lin; Yi-Qing Li; Yu-Fei Xie; Zhong-Wei Li; Xu-Guang Guo (Biochemical Genetics, 2022)
COVID-19 is a serious infectious disease that has recently swept the world, and research on its causative virus, SARS-CoV-2, remains insufficient. Therefore, this study uses bioinformatics analysis techniques to explore the human digestive tract diseases that may be caused by SARS-CoV-2 infection. The gene expression profile data set, numbered GSE149312, is from the Gene Expression Omnibus (GEO) database and is divided into a 24-h group and a 60-h group. R software is used to analyze and screen out differentially expressed genes (DEGs) and then gene ontology (GO) term and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses are performed. In KEGG, the pathway of non-alcoholic fatty liver disease exists in both the 24-h group and 60-h group. STRING is used to establish a protein–protein interaction (PPI) network, and Cytoscape is then used to visualize the PPI and define the top 12 genes of the node as the hub genes. Through verification, nine statistically significant hub genes are identified: AKT1, TIMP1, NOTCH, CCNA2, RRM2, TTK, BUB1B, KIF20A, and PLK1. In conclusion, the results of this study can provide a certain direction and basis for follow-up studies of SARS-CoV-2 infection of the human digestive tract and provide new insights for the prevention and treatment of diseases caused by SARS-CoV-2.

Double-phase-shift filtering method for harmonic elimination based on AR2U-Net - Bo-Lin Li; Yan-Chun Wang; Hang Yuan; Xue-Qing Liu (Applied Geophysics, 2022)

First report of chilli veinal mottle virus infecting tobacco in Guizhou, China - Yue Chen; Ting Ting Li; Jing Zhong; Li Ling Zhao; Ya Li Guo; Ye Chun Lin; Gui Gao; Yi Cao; Ming Ding (Journal of Plant Pathology, 2022)

Pinirhizobacter soli gen. nov., sp. nov., a novel low temperature resistant gammaproteobacterium in the family Rhodanobacteraceae isolated from rhizospheric soil of Larix gmelinii - Han Xue; Chun-gen Piao; Ying-hua Lin; Yong Li (Archives of Microbiology, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Feasibility and usability of a mobile health tool on anticoagulation management for patients with atrial fibrillation: a pilot study - Chi Zhang; Mang-Mang Pan; Na Wang; Wei-Wei Wang; Zheng Li; Zhi-Chun Gu; Hou-Wen Lin (European Journal of Clinical Pharmacology, 2022)

Individual exposure to ambient PM2.5 and hospital admissions for COPD in 110 hospitals: a case-crossover study in Guangzhou, China - Jie-Qi Jin; Dong Han; Qi Tian; Zhao-Yue Chen; Yun-Shao Ye; Qiao-Xuan Lin; Chun-Quan Ou; Li Li (Environmental Science and Pollution Research, 2022)
Few studies have evaluated the short-term association between hospital admissions and individual exposure to ambient particulate matter (PM 2.5 ). Particularly, no studies focused on hospital admissions for chronic obstructive pulmonary disease (COPD) at the individual level. We assessed the short-term effects of PM 2.5 on hospitalization admissions for COPD in Guangzhou, China, during 2014–2015, based on satellite-derived estimates of ambient PM 2.5 concentrations at a 1-km resolution near the residential address as individual-level exposure for each patient. Around 40,002 patients with COPD admitted to 110 hospitals were included in this study. A time-stratified case-crossover design with conditional logistic regression models was applied to assess the effects of PM 2.5 based on a 1-km grid data of aerosol optical depth provided by the National Aeronautics and Space Administration on hospital admissions for COPD. Further, we performed stratified analyses by individual demographic characteristics and season of hospital admission. Around 10 μg/m 3 increase in individual-level PM 2.5 was associated with an increase of 1.6% (95% confidence interval [CI]: 0.6%, 2.7%) in hospitalization for COPD at a lag of 0–5 days. The impact of PM 2.5 on hospitalization for COPD was greater significantly in males and patients admitted in summer. Our study strengthened the evidence for the adverse effect of PM 2.5 based on satellite-based individual-level exposure data.

Advenella mandrilli sp. nov., a bacterium isolated from the faeces of Mandrillus sphinx - Qiong Wang; Xiu-Lin Han; Zhi-Qin Fang; Chen-Lu Zhang; Chun Li; Tao Lu (Antonie van Leeuwenhoek, 2022)

Ethylene insensitive mutation alleviates cadmium-induced photosynthesis impairment in Arabidopsis plants - Qi-Yu Zhao; Chun-Xiu Gu; Yu Wang; Guang-Zhe Li; Lin Hao (Acta Physiologiae Plantarum, 2022)

New paraconic acids from the endophytic fungus Xylariaceae sp. J4 - Chao Yuan; Xue-Chun Shu; Lin Fan; Ying-Bo Zhang; Ling-Liang Guan; Fu-Lai Yu; Xiao-Lu Chen; Gang Li (Natural Product Research, 2022)

Sabulicella rubraurantiaca gen. nov., sp. nov., a new member of the family Acetobacteraceae, isolated from desert soil - Zhi-Liang Lin; Shuai Li; Qi-Chuang Wei; Wen-Hui Lian; Chun-Yan Lu; Lu Xu; Li-Nan Huang; Lei Dong; Wen-Jun Li (Archives of Microbiology, 2022)

Microorganism and Physiochemical Characteristic of High-salt (Suan Yu), a Traditional Chinese Fermented Fish - Chengxing Lin; Furong Zhang; Qin Yang; Ju Meng; Laping He; Li Deng; Chun Ye; Xuefeng Zeng (Journal of Aquatic Food Product Technology, 2021)

NRG1 accelerates the forgetting of fear memories and facilitates the induction of long-term depression in adult mice - Qianqian Cao; Yuan Wei; Jialin Deng; Junfeng Li; Yanhua Huang; Yuke Li; Ji-chun Zhang; Zili Zhang; Song Lin (Psychopharmacology, 2021)

Wogonin Accelerates Hematoma Clearance and Improves Neurological Outcome via the PPAR-γ Pathway After Intracerebral Hemorrhage - Jianfeng Zhuang; Yucong Peng; Chi Gu; Huihui Chen; Zheng Lin; Hang Zhou; Xiao Wu; Jianru Li; Xiaobo Yu; Yang Cao; Hanhai Zeng; Xiongjie Fu; et al. (Translational Stroke Research, 2021)

Nucleophosmin/B23 promotes endometrial cancer cell escape from macrophage phagocytosis by increasing CD24 expression - Chiao-Yun Lin; Chia-Lung Tsai; Angel Chao; Li-Yu Lee; Wei-Chun Chen; Yun-Hsin Tang; An-Shine Chao; Chyong-Huey Lai (Journal of Molecular Medicine, 2021)

Overexpression of Cell-Surface Marker SLC16A1 Shortened Survival in Human High-Grade Gliomas - Hong-Han Lin; Wen-Chiuan Tsai; Chia-Kuang Tsai; Ssu-Han Chen; Li-Chun Huang; Dueng-Yuan Hueng; Kuang-Chen Hung (Journal of Molecular Neuroscience, 2021)

RSF1 requires CEBP/β and hSNF2H to promote IL-1β-mediated angiogenesis: the clinical and therapeutic relevance of RSF1 overexpression and amplification in myxofibrosarcomas - Chien-Feng Li; Ti-Chen Chan; Cheng-I. Wang; Fu-Min Fang; Po-Chun Lin; Shih-Chen Yu; Hsuan-Ying Huang (Angiogenesis, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Evidence-based Customized Ankle-Foot Orthosis with Energy Storage - Chih-Chun Lin; Chien-Hsien Yeh; Yi-Chun Tsai; Li-Chieh Kuo; Hsiu-Yun Hsu; Ping-Han Chuang; Kai Chang; Fong-Chin Su (Journal of Medical and Biological Engineering, 2021)

Effects of plant growth regulators and polyamines on bract longevity in Bougainvillea buttiana - Kuan-Hung Lin; Jui-Mei Li; Chun-Wei Wu; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

BDS signal-in-space anomaly probability analysis over the last 6 years - Yuxin Zhao; Chun Cheng; Liang Li; Renlong Wang; Yuanyuan Liu; Zishen Li; Lin Zhao (GPS Solutions, 2021)

miR-23b Attenuates LPS-Induced Inflammatory Responses in Acute Lung Injury via Inhibition of HDAC2 - Zhi-Feng Luo; Xiang-Hui Jiang; Huan Liu; Li-Yuan He; Xiong Luo; Fu-Chun Chen; Yu-Lin Tan (Biochemical Genetics, 2021)

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Sesquiterpenoids and meroterpenoids from a mangrove derived fungus Diaporthe sp. SCSIO 41011 - Xiao-Wei Luo; Chun-Mei Chen; Kun-Long Li; Xiu-Ping Lin; Cheng-Hai Gao; Xue-Feng Zhou; Yong-Hong Liu (Natural Product Research, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Typical gene expression profile of pseudorabies virus reactivation from latency in swine trigeminal ganglion - Hai-Hua Wang; Jie Liu; Lin-Tao Li; Huan-Chun Chen; Wan-Po Zhang; Zheng-Fei Liu (Journal of NeuroVirology, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Future trends and guidance for the triple bottom line and sustainability: a data driven bibliometric analysis - Ming-Lang Tseng; Chia-Hao Chang; Chun-Wei Remen Lin; Kuo-Jui Wu; Qing Chen; Li Xia; Bing Xue (Environmental Science and Pollution Research, 2020)
This study conducts a comprehensive literature review of articles on the triple bottom line (TBL) published from January 1997 to September 2018 to provide significant insights and support to guide further discussion. There were three booms in TBL publications, occurring in 2003, 2011, and 2015, and many articles attempt to address the issue of sustainability by employing the TBL. This literature analysis includes 720, 132, and 58 articles from the Web of Science (WOS), Inspec, and Scopus databases, respectively, and reveals the gaps in existing research. To discover the barriers and points of overlap, these articles are categorized into six aspects of the TBL: economic, environmental, social, operations, technology, and engineering. Examining the top 3 journals in terms of published articles on each aspect reveals the research trends and gaps. The findings provide solid evidence confirming the argument that the TBL as currently defined is insufficient to cover the entire concept of sustainability. The social and engineering aspects still require more discussion to support the linkage of the TBL and to reinforce its theoretical basis. Additionally, to discover the gaps in the data sources, theories applied, methods adopted, and types of contributions, this article summarizes 82 highly cited articles covering each aspect. This article offers theoretical insights by identifying the top contributing countries, institutions, authors, keyword networks, and authorship networks to encourage scholars to push the current discussion further forward, and it provides practical insights to bridge the gap between theory and practice for enhancing the efficiency and effectiveness of improvements.

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

Anthraquinone derivatives from a coral associated fungus Stemphylium lycopersici - Jiao Li; Yu-Bing Zheng; Tibor Kurtán; Ming-Xiang Liu; Hua Tang; Chun-Lin Zhuang; Wen Zhang (Natural Product Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Acanthophoraine A, a new pyrrolidine alkaloid from the red alga Acanthophora spicifera - Jia-Li Lin; Yong-Qian Liang; Xiao-Jian Liao; Jian-Ting Yang; Dai-Chun Li; Yu-Ling Huang; Zhi-Hui Jiang; Shi-Hai Xu; Bing-Xin Zhao (Natural Product Research, 2020)

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

Whole brain radiotherapy induces cognitive dysfunction in mice: key role of gut microbiota - Xiao-Xiao Luo; Chun Yang; Gao-Feng Zhan; Shan Li; Dong-Yu Hua; Ai-Lin Luo; Xiang-Lin Yuan (Psychopharmacology, 2020)

Dynamic response and mechanical deformation properties of the soil cutting slope under train cyclic loads - Qiang Xie; Zhi-hui Wu; Chun-bo He; Jie Dong; Zhi-lin Cao; Li Liang (Arabian Journal of Geosciences, 2020)

Modulation of copper-induced antioxidant defense, Cu transport, and mitophagy by hypoxia in the large yellow croaker (Larimichthys crocea) - Yun Pan; Chun-Xiang Ai; Lin Zeng; Can Liu; Wen-Cheng Li (Fish Physiology and Biochemistry, 2020)

The occurrence and spatial distribution of phthalate esters (PAEs) in the Lanzhou section of the Yellow River - Xia Zhao; Ji-min Shen; Hang Zhang; Xiang Li; Zhong-lin Chen; Xiao-chun Wang (Environmental Science and Pollution Research, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

First report of powdery mildew on Bidens pilosa var. radiata and Passiflora edulis f. flavicarpa caused by Golovinomyces circumfusus in Taiwan - Tsung-Chun Lin; Yu-Lun Dai; Cing-Siang You; Jenn-Wen Huang; Chih-Li Wang (Journal of Plant Pathology, 2020)

Effects of small nucleolar RNA SNORD44 on the proliferation, apoptosis and invasion of glioma cells - Xian-Ru Xia; Wen-Cui Li; Zong-Tao Yu; Jie Li; Chun-Yan Peng; Li Jin; Guo-Lin Yuan (Histochemistry and Cell Biology, 2020)

Cross-Strait climate change and agricultural product loss - Hsing-Chun Lin; Li-Chen Chou; Wan-Hao Zhang (Environmental Science and Pollution Research, 2020)

Integrity monitoring of carrier phase-based ephemeris fault detection - Liang Li; Xiaosong Liu; Chun Jia; Chun Cheng; Jiaxiang Li; Lin Zhao (GPS Solutions, 2020)

Abundance and residency dynamics of the Indo‐Pacific humpback dolphin, Sousa chinensis , in the Dafengjiang River Estuary, China - Chongwei Peng; Haiping Wu; Xianyan Wang; Qian Zhu; Thomas A. Jefferson; Chun‐Chieh Wang; Youhou Xu; Jian Li; Hu Huang; Mo Chen; Shiang‐Lin Huang (Marine Mammal Science, 2020)
Robust population size estimates are essential for informing population conservation status. Residency dynamics show population habitat use through time. Population size of Indo‐Pacific humpback dolphins ( Sousa chinensis ) has been extensively investigated in Chinese waters, but their residency dynamics are rarely known. Mark‐recapture analysis based on photo‐identification records was applied to humpback dolphins in the Dafengjiang River Estuary habitat, one of the key habitats in the northern Beibu Gulf, China. Movement analyses based on lagged identification rate indicated the humpback dolphins spent, on average, 78.5 days inside and 46.9 days outside the survey area. Within the study area, the humpback dolphin abundance was 83 identifiable dolphins. A total of 353–430 humpback dolphins, estimated by POPAN modeling, were involved in this fluid habitat‐use dynamic. Robust Design analysis showed strong seasonality in humpback dolphin abundance and emigration probability, implying a movement‐ and habitat‐use pattern likely associated with spatiotemporal distribution of oceanographic characteristics and prey occurrences. Population surveys and conservation measures currently conducted in Chinese waters seldom consider seasonality in movements between habitat patches, which can be addressed by genetic analyses across habitats and cross‐matching photo‐identification records among neighboring habitats.

Instantaneous phase inversion based on an unwrapping algorithm - Yu-Zhao Lin; Zhen-Chun Li; Kai Zhang; Ren-Wei Ding; Ping Jiang (Applied Geophysics, 2020)

The Arabidopsis kinase-associated protein phosphatase KAPP, interacting with protein kinases SnRK2.2/2.3/2.6, negatively regulates abscisic acid signaling - Kai Lu; Ya-Dong Zhang; Chun-Fang Zhao; Li-Hui Zhou; Qing-Yong Zhao; Tao Chen; Cai-Lin Wang (Plant Molecular Biology, 2020)

Cloning and Expression Analysis of the ScD53 Gene from Sugarcane - Ai-Li Lv; Xu-Juan Li; Chun-Jia Li; Hong-Bo Liu; Qiu-Yan Zi; Xiu-Qin Lin; Xin-Long Liu (Sugar Tech, 2019)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Potential role of IL-37 signaling pathway in feedback regulation of autoimmune Hashimoto thyroiditis - Cui-Ping Ren; Li Sun; Feng-Chun Liu; Chun-Lin Zuo; Miao Liu; Wenda Gao; Ji-Jia Shen (Histochemistry and Cell Biology, 2019)

Autotrophic Bacterial Community and Microbial CO2 Fixation Respond to Vegetation Restoration of Eroded Agricultural Land - Haibing Xiao; Zhongwu Li; Chuxiong Deng; Lin Liu; Jia Chen; Bin Huang; Xiaodong Nie; Chun Liu; Danyang Wang; Jieyu Jiang (Ecosystems, 2019)

Aflatoxin B1 enhances pyroptosis of hepatocytes and activation of Kupffer cells to promote liver inflammatory injury via dephosphorylation of cyclooxygenase-2: an in vitro, ex vivo and in vivo study - Li-Yin Zhang; Deng-Lin Zhan; Yuan-Yuan Chen; Wei-Hua Wang; Cheng-Yong He; Yi Lin; Yu-Chun Lin; Zhong-Ning Lin (Archives of Toxicology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

Pivot single-difference ambiguity resolution for multi-GNSS positioning with non-overlapping frequencies - Chun Jia; Lin Zhao; Liang Li; Yang Gao; Yuting Gao (GPS Solutions, 2019)

Rab18 Collaborates with Rab7 to Modulate Lysosomal and Autophagy Activities in the Nervous System: an Overlapping Mechanism for Warburg Micro Syndrome and Charcot-Marie-Tooth Neuropathy Type 2B - Fang-Shin Nian; Lei-Li Li; Chih-Ya Cheng; Pei-Chun Wu; You-Tai Lin; Cheng-Yung Tang; Bo-Shiun Ren; Chin-Yin Tai; Ming-Ji Fann; Lung-Sen Kao; Chen-Jee Hong; Jin-Wu Tsai (Molecular Neurobiology, 2019)

Research on the effect of coal seam inclination on gas migration channels at fully mechanized coal mining face - Pengxiang Zhao; Risheng Zhuo; Shugang Li; Chun-Hsing Ho; Haifei Lin; Hui Liu (Arabian Journal of Geosciences, 2019)

Removal of chlorpheniramine and variations of nitrosamine formation potentials in municipal wastewaters by adsorption onto the GO-Fe3O4 - Chih-Hsien Lin; Chi-Min Li; Chun-Hu Chen; Wei-Hsiang Chen (Environmental Science and Pollution Research, 2019)

Exosomal long non-coding RNAs: biological properties and therapeutic potential in cancer treatment - Jie Luo; Yan Xiong; Pei-fen Fu; En-chun Li; Lei Qu; Xiao Fan; Zhi-jian Cai; Ai-fu Lin (Journal of Zhejiang University-SCIENCE B, 2019)

First Report on Toxoplasma gondii Seroprevalence in Free-Ranging Pigs in Northeastern China - Qi Li; Si-Yuan Qin; Shuo Li; Peng Peng; Quan Zhao; Hong-Lin Jia; Chun-Ren Wang (Acta Parasitologica, 2019)

Health risk of metal exposure via inhalation of cigarette sidestream smoke particulate matter - Li-Chuan Cheng; Chun-Ju Lin; Huei-Ju Liu; Lih-Ann Li (Environmental Science and Pollution Research, 2019)

l-Carnitine inhibits the senescence-associated secretory phenotype of aging adipose tissue by JNK/p53 pathway - Lian-wei Yang; Ming Song; Yu-lin Li; Ya-peng Liu; Chun Liu; Lu Han; Zhi-hao Wang; Wei Zhang; Yan-qiu Xing; Ming Zhong (Biogerontology, 2019)

Prediction of annual dengue incidence by hydro-climatic extremes for southern Taiwan - Hsiang-Yu Yuan; Tzai-Hung Wen; Yi-Hung Kung; Hsiao-Hui Tsou; Chun-Hong Chen; Li-Wei Chen; Pei-Sheng Lin (International Journal of Biometeorology, 2019)

Analysis of Electroencephalography Event-Related Desynchronisation and Synchronisation Induced by Lower-Limb Stepping Motor Imagery - Yi-Hung Liu; Li-Fong Lin; Chun-Wei Chou; Yun Chang; Yu-Tsung Hsiao; Wei-Chun Hsu (Journal of Medical and Biological Engineering, 2019)

Detection and quantification of Aeromonas schubertii in Channa maculata by TaqMan MGB probe fluorescence real‐time quantitative PCR - Chun Liu; Yanming M. Guo; Jizhen Z. Cao; De‐Feng Zhang; Ou‐Qin Chang; Kaibin Li; Fang Wang; Cun‐Bin Shi; Lan Jiang; Qing Wang; Li Lin (Journal of Fish Diseases, 2019)
Aeromonas schubertii is a major epidemiological agent that threatens cultured snakeheads ( Channidae ) and has caused great economic losses in fish‐farming industries in China in recent years. In present study, a specific TaqMan minor groove binder ( MGB ) probe fluorescence real‐time quantitative PCR ( qPCR ) assay was developed to rapidly detect and quantify A. schubertii . A pair of qPCR primers and a TaqMan MGB probe were selected from the rpoD gene, which were shown to be specific for A. schubertii . A high correlation coefficient ( R 2 = 0.9998) in a standard curve with a 103% efficiency was obtained. Moreover, the qPCR method's detection limit was as low as 18 copies/μl, which was 100 times more sensitive than that of conventional PCR . The detection results for the A. schubertii in pond water and fish tissue were consistent with those of the viable counts. Bacterial load changes detected by qPCR in different tissues of snakeheads infected with A. schubertii showed that the gills and intestines may be the entry for A. schubertii , and the spleen and kidney are major sites for A. schubertii replication. The established method in present study should be a useful tool for the early surveillance and quantitation of A. schubertii .

Dopamine receptor D2 polymorphism is associated with alleviation of obesity after 8-year follow-up: a retrospective cohort study in obese Chinese children and adolescents - Jian-fang Zhu; Lian-hui Chen; Ke Yuan; Li Liang; Chun-lin Wang (Journal of Zhejiang University-SCIENCE B, 2018)

Integrity monitoring of high-accuracy GNSS-based attitude determination - Na Li; Lin Zhao; Liang Li; Chun Jia (GPS Solutions, 2018)

Microbial CO2 assimilation is not limited by the decrease in autotrophic bacterial abundance and diversity in eroded watershed - Haibing Xiao; Zhongwu Li; Xiaofeng Chang; Lei Deng; Xiaodong Nie; Chun Liu; Lin Liu; Jieyu Jiang; Jia Chen; Danyang Wang (Biology and Fertility of Soils, 2018)

Finite element response sensitivity analysis of three-dimensional soil-foundation-structure interaction (SFSI) systems - Quan Gu; Yongdou Liu; Yong Li; Chun Lin (Earthquake Engineering and Engineering Vibration, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Identifying crack initiation stress threshold in brittle rocks using axial strain stiffness characteristics - Mei-ben Gao; Tian-bin Li; Lu-bo Meng; Chun-chi Ma; Hui-lin Xing (Journal of Mountain Science, 2018)

The complete mitochondrial genome of Kele pig (Sus scrofa) using next-generation deep sequencing - Ya Tan; Kai-zhi Shi; Jing Wang; Chun-lin Du; Chun-ping Zhao; Xiong Zhang; Li Zhu; Yi-shun Shang (Conservation Genetics Resources, 2018)

Long-term study on seasonal changes in floristic composition and structure of marine macroalgal communities along the coast of Northern Taiwan, southern East China Sea - Showe-Mei Lin; Li-Chun Tseng; Put O. Ang; John Bolton; Li-Chia Liu (Marine Biology, 2018)

Position-domain integrity risk-based ambiguity validation for the integer bootstrap estimator - Liang Li; Haodong Shi; Chun Jia; Jianhua Cheng; Hui Li; Lin Zhao (GPS Solutions, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

Estimation of the daily soil/dust (SD) ingestion rate of children from Gansu Province, China via hand-to-mouth contact using tracer elements - Jin Ma; Li-bo Pan; Qin Wang; Chun-ye Lin; Xiao-li Duan; Hong Hou (Environmental Geochemistry and Health, 2018)

Activation of PXR inhibits LPS-induced NF-κB activation by increasing IκBα expression in HepG2 cells - Nanhui Ye; Hang Wang; Qiaoling Li; Chaotong Lin; Huahua Feng; Suying Lin; Jing Hong; Chun Meng (Molecular & Cellular Toxicology, 2018)

Time-domain wavefield reconstruction inversion - Zhen-Chun Li; Yu-Zhao Lin; Kai Zhang; Yuan-Yuan Li; Zhen-Nan Yu (Applied Geophysics, 2017)

Postural Stability Assessment in Patients with Mild Traumatic Brain Injury Complaining of Dizziness - Kai-Yun Chen; Shih-Wei Huang; Yen-Nung Lin; Chun-De Liao; Wen-Hsuan Hou; Tsan-Hon Liou; Yung-Hsiao Chiang; Shin-Han Tsai; Wen-Ta Chiu; Wei-Chun Hsu; Li-Fong Lin (Journal of Medical and Biological Engineering, 2017)

Impacts of precipitation variation and soil and water conservation measures on runoff and sediment yield in the Loess Plateau Gully Region, China - Lu Xia; Xiao-yu Song; Na Fu; Chun-fang Meng; Huai-you Li; Yao-lin Li (Journal of Mountain Science, 2017)

Integrity and continuity allocation for the RAIM with multiple constellations - Liang Li; Huan Wang; Chun Jia; Lin Zhao; Yuxin Zhao (GPS Solutions, 2017)

The complete mitochondrial genome of Budorcas taxicolor bedfordi (Artiodactyla: Bovidae) and phylogenetic studies of Caprinae - Mao-hong Sun; Chun-wang Yue; Ting-ting Liu; Lin Li; Hai-ying Liu (Conservation Genetics Resources, 2017)

Suppressive effect of microRNA319 expression on rice plant height - Wei-Ting Liu; Peng-Wen Chen; Li-Chi Chen; Chia-Chun Yang; Shu-Yun Chen; GuanFu Huang; Tzu Che Lin; Hsin-Mei Ku; Jeremy J. W. Chen (Theoretical and Applied Genetics, 2017)

Identification of manganese-toxicity-responsive genes in roots of two citrus species differing in manganese tolerance using cDNA-AFLP - Chen-Ping Zhou; Chun-Ping Li; Wei-Wei Liang; Peng Guo; Lin-Tong Yang; Li-Song Chen (Trees, 2017)

Molecular and morphological identification of a human biting tick, Amblyomma testudinarium (Acari: Ixodidae), in Taiwan - Li-Lian Chao; Chun-Wei Lu; Ying-Fang Lin; Chien-Ming Shih (Experimental and Applied Acarology, 2017)

Integrity monitoring-based ambiguity validation for triple-carrier ambiguity resolution - Liang Li; Chun Jia; Lin Zhao; Fuxin Yang; Zishen Li (GPS Solutions, 2017)

Comparative Efficacy and Safety of Nine Anti-Platelet Therapies for Patients with Ischemic Stroke or Transient Ischemic Attack: a Mixed Treatment Comparisons - Hua-Pin Huang; Wan-Hui Lin; Sheng-Gen Chen; Li-Zhen Chen; Min-Yi Chen; Chun-Hui Che (Molecular Neurobiology, 2017)

Complete genomic characterization of two European-genotype porcine reproductive and respiratory syndrome virus isolates in Fujian province of China - Jian-Kui Liu; Chun-Hua Wei; AI-Ling Dai; Ke-Wei Fan; Bing-Hui Yang; Chun-Fang Huang; Xiao-Hua Li; Xiao-Yan Yang; Man-Lin Luo (Archives of Virology, 2017)

Predatory efficiency of the copepod Megacyclops formosanus and toxic effect of the red alga Gracilaria firma-synthesized silver nanoparticles against the dengue vector Aedes aegypti - Kandasamy Kalimuthu; Chellasamy Panneerselvam; Chi Chou; Showe-Mei Lin; Li-Chun Tseng; Kun-Hsien Tsai; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2017)

Effects of soybean isoflavone on intestinal antioxidant capacity and cytokines in young piglets fed oxidized fish oil - Lin Huang; Xian-yong Ma; Zong-yong Jiang; You-jun Hu; Chun-tian Zheng; Xue-fen Yang; Li Wang; Kai-guo Gao (Journal of Zhejiang University-SCIENCE B, 2016)

Tripchlorolide Attenuates β-amyloid Generation via Suppressing PPARγ-Regulated BACE1 Activity in N2a/APP695 Cells - Nan Lin; Li-min Chen; Xiao-dong Pan; Yuan-gui Zhu; Jing Zhang; Yan-qing Shi; Xiao-chun Chen (Molecular Neurobiology, 2016)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Aneuploid progenies of triploid hybrids between diploid and tetraploid loach Misgurnus anguillicaudatus in China - Ya-Juan Li; Yang-Chun Gao; He Zhou; Hai-Yan Ma; Zhong-Qiao Lin; Tian-Yu Ma; Yi Sui; Katsutoshi Arai (Genetica, 2016)

In Situ Field-Scale Remediation of Low Cd-Contaminated Paddy Soil Using Soil Amendments - Lin-feng Li; Shao-ying Ai; Yan-hong Wang; Ming-deng Tang; Yi-Chun Li (Water, Air, & Soil Pollution, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Brittle Rock Modeling Approach and its Validation Using Excavation-Induced Micro-Seismicity - Chun-Chi Ma; Tian-Bin Li; Hui-Lin Xing; Hang Zhang; Min-Jie Wang; Tian-Yi Liu; Guo-Qing Chen; Zi-Quan Chen (Rock Mechanics and Rock Engineering, 2016)

Factorial Analysis of Variables Influencing Mechanical Characteristics in Le Fort I Osteotomy Using FEA and Statistics-Based Taguchi Method - Shao-Fu Huang; Lun-Jou Lo; Chun-Li Lin (Journal of Medical and Biological Engineering, 2016)

From folding to transpressional faulting: the Cenozoic Fusha structural belt in front of the Western Kunlun Orogen, northwestern Tibetan Plateau - Cong Wang; Xiao-Gan Cheng; Han-Lin Chen; Kang Li; Xiao-Gen Fan; Chun-Yang Wang (International Journal of Earth Sciences, 2016)

Biotransformation of gypenoside XVII to compound K by a recombinant β-glucosidase - Fei-Liang Zhong; Wei-Wei Dong; Songquan Wu; Jun Jiang; Deok-Chun Yang; Donghao Li; Lin-Hu Quan (Biotechnology Letters, 2016)

QTL mapping of dehiscence length at the basal part of thecae related to heat tolerance of rice (Oryza sativa L.) - Ling Zhao; Chun-Fang Zhao; Li-Hui Zhou; Jing Lin; Qing-Yong Zhao; Zhen Zhu; Tao Chen; Shu Yao; Toshihiro Hasegawa; Tsutomu Matsui; Cai-Lin Wang (Euphytica, 2016)

A new phenolic compound with antioxidant activity from the branches and leaves of Pyrus pashia - Zhen-Jie Li; Xi Zheng; Chun-Ping Wan; Le Cai; Ying Li; Lin Huang; Zhong-Tao Ding (Natural Product Research, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Phylogenetic relationships and Y genome origin in Kengyilia (Triticeae: Poaceae) based on single copy gene DMC1 - Gang Gao; Zi-lin Tang; Jia-bin Deng; Xue-mei Gou; Qian Wang; Yan Zhang; Chun-bang Ding; Li Zhang; Yong-hong Zhou; Rui-wu Yang (Biologia, 2016)

Mono(2-ethylhexyl)phthalate accumulation disturbs energy metabolism of fat cells - Huai-chih Chiang; Ya-Ting Kuo; Chih-Che Shen; Yi-Hua Lin; Shu-Li Wang; Tsui-Chun Tsou (Archives of Toxicology, 2016)

Species-specific differences in the role of L-type Ca2+ channels in the regulation of coronary arterial smooth muscle contraction - Hui Yang; Su-Juan Kuang; Fang Rao; Yu-Mei Xue; Xiao-Ying Liu; Zhi-Xin Shan; Xiao-Hong Li; Jie-Ning Zhu; Zhi-Ling Zhou; Xiao-juan Zhang; Qiu-Xiong Lin; Xi-Yong Yu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Prenatal molecular cytogenetic analysis of a mild dysmorphic fetus with a huge unbalance karyotype involving partial 9p deletion and partial 18q duplication - Yueh-Chun Li; Yi-Ju Pan; Fuu-Jen Tsai; Chyi-Chyang Lin (Genes & Genomics, 2016)

Development of single-chain variable fragments (scFv) against influenza virus targeting hemagglutinin subunit 2 (HA2) - Tai-Wei Li; Shu-Fang Cheng; Yen-Tzu Tseng; Yu-Chih Yang; Wen-chun Liu; Sheng-Cyuan Wang; Mei-Ju Chou; Yu-Jen Lin; Yueh Wang; Pei-Wen Hsiao; Suh-Chin Wu; Ding-Kwo Chang (Archives of Virology, 2016)

Separation and identification of a novel tadalafil analogue adulterant in a dietary supplement - Yen-Chun Huang; Hui-Chun Lee; Yun-Lian Lin; Chia-Ying Li; Chia-Fen Tsai; Hwei-Fang Cheng (Food Additives & Contaminants: Part A, 2015)

Identification of two novel critical mutations in PCNT gene resulting in microcephalic osteodysplastic primordial dwarfism type II associated with multiple intracranial aneurysms - Fei-Feng Li; Xu-Dong Wang; Min-Wei Zhu; Zhi-Hong Lou; Qiong Zhang; Chun-Yu Zhu; Hong-Lin Feng; Zhi-Guo Lin; Shu-Lin Liu (Metabolic Brain Disease, 2015)

Impact of phloem girdling on water status in desert plants Alhagi sparsifolia Shap. (Fabaceae) and Karelinia Caspica (Pall.) Less. (Asteraceae) - Gang-liang Tang; Xiang-yi Li; Li-sha Lin; Zi-chun Guo; Chang-jun Li; Hui Guo; Fan-jiang Zeng (Brazilian Journal of Botany, 2015)

Using hybrid transcription factors to study gene function in rice - Tao Zhao; Jun Liu; Hong-Yu Li; Jian-Zhong Lin; Ming-Di Bian; Chun-Yu Zhang; Yong-Xing Zhang; Yu-Chong Peng; Bin Liu; ChenTao Lin (Science China Life Sciences, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Assessing the early changes of cerebral glucose metabolism via dynamic 18FDG-PET/CT during cardiac arrest - Ying-Qing Li; Xiao-Xing Liao; Jian-Hua Lu; Rong Liu; Chun-Lin Hu; Gang Dai; Xiang-Song Zhang; Xin-Chong Shi; Xin Li (Metabolic Brain Disease, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

Structural transformation of oyster, hard clam, and sea urchin shells after calcination and their antibacterial activity against foodborne microorganisms - Yu-Chun Chen; Chun-Lan Lin; Chih-Ting Li; Deng-Fwu Hwang (Fisheries Science, 2015)

TM-1-1DP exerts protective effect against myocardial ischemia reperfusion injury via AKT-eNOS pathway - Hui-Chun Ku; Shih-Yi Lee; Chi-Hsuan Chen; Yao-Hsing Wang; Chin-Ting Lin; Shoei-Sheng Lee; Ting-Hsuan Li; Ming-Jai Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Inhibition of isoflavone biosynthesis enhanced T-DNA delivery in soybean by improving plant–Agrobacterium tumefaciens interaction - Yan-Min Zhang; Hong-Mei Zhang; Zi-Hui Liu; Xiu-Lin Guo; Hui-Cong Li; Guo-Liang Li; Chun-Zhi Jiang; Meng-Chen Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Erratum to: Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2015)

Human health risk assessment of soil dioxin/furans contamination and dioxin-like activity determined by ethoxyresorufin-O-deethylase bioassay - Yu Bon Man; Ka Lai Chow; Hong Sheng Wang; Xiao Lin Sun; Sheng Chun Wu; Zong Wei Cai; Yuan Kang; Hui Li; Jin Shu Zheng; John P. Giesy; Ming Hung Wong (Environmental Science and Pollution Research, 2015)

Chryseobacterium profundimaris sp. nov., a new member of the family Flavobacteriaceae isolated from deep-sea sediment - Lin Xu; Ying-Yi Huo; Zheng-Yang Li; Chun-Sheng Wang; Aharon Oren; Xue-Wei Xu (Antonie van Leeuwenhoek, 2015)

Characteristics of Na+ uptake in sugar beet (Beta vulgaris L.) seedlings under mild salt conditions - Guo-Qiang Wu; Qing-Zhao Shui; Chun-Mei Wang; Jin-Lin Zhang; Hui-Jun Yuan; Shan-Jia Li; Zuo-Jun Liu (Acta Physiologiae Plantarum, 2015)

Production and Characteristics of High Quality Vinegar from Sugarcane Juice - Gan-Lin Chen; Feng-Jin Zheng; Jian Sun; Zhi-Chun Li; Bo Lin; Yang-Rui Li (Sugar Tech, 2015)

A Brassica napus PHT1 phosphate transporter, BnPht1;4, promotes phosphate uptake and affects roots architecture of transgenic Arabidopsis - Feng Ren; Cai-Zhi Zhao; Chun-Sen Liu; Ke-Lin Huang; Qian-Qian Guo; Li-Li Chang; Huan Xiong; Xue-Bao Li (Plant Molecular Biology, 2014)

MiR-199a is overexpressed in plasma of type 2 diabetes patients which contributes to type 2 diabetes by targeting GLUT4 - Shuang-Tong Yan; Chun-Lin Li; Hui Tian; Jian Li; Yu Pei; Yu Liu; Yan-Ping Gong; Fu-Sheng Fang; Ban-Ruo Sun (Molecular and Cellular Biochemistry, 2014)

Bio-efficacy potential of seaweed Gracilaria firma with copepod, Megacyclops formosanus for the control larvae of dengue vector Aedes aegypti - Kandasamy Kalimuthu; Show-Mei Lin; Li-Chun Tseng; Kadarkarai Murugan; Jiang-Shiou Hwang (Hydrobiologia, 2014)

Local adaptation and phenotypic plasticity both occurred in Wedelia trilobata invasion across a tropical island - Chun-Can Si; Zhi-Cong Dai; Ying Lin; Shan-Shan Qi; Ping Huang; Shi-Li Miao; Dao-Lin Du (Biological Invasions, 2014)

Short-term effects of meteorological factors on children hand, foot and mouth disease in Guangzhou, China - Chun Chen; Hualiang Lin; Xiaoquan Li; Lingling Lang; Xincai Xiao; Peng Ding; Peng He; Ying Zhang; Ming Wang; Qiyong Liu (International Journal of Biometeorology, 2014)

An Effective Method of Isolating Endothelial Cells from Intact Rat Aorta - Hua Tian; Ning Suo; Fei Li; Chun-Lin Yang; Xiao Qiong (Cell Biochemistry and Biophysics, 2014)

Effects of Bone Marrow Mesenchymal Stem Cells on Hematopoietic Recovery and Acute Graft-Versus-Host Disease in Murine Allogeneic Umbilical Cord Blood Transplantation Model - Zhen Yu Li; Chun Qing Wang; Guang Lu; Xiu Ying Pan; Kai Lin Xu (Cell Biochemistry and Biophysics, 2014)

Tomato plant growth promotion and antibacterial related-mechanisms of four rhizobacterial Bacillus strains against Ralstonia solanacearum - Abdulwareth A. Almoneafy; Kaleem Ullah Kakar; Zarqa Nawaz; Bin Li; Mumtaz Ali saand; Yang Chun-lan; Guan-Lin Xie (Symbiosis, 2014)

3D topographic correction of the BSR heat flow and detection of focused fluid flow - Tao He; Hong-Lin Li; Chang-Chun Zou (Applied Geophysics, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Endophytic nitrogen-fixing Klebsiella variicola strain DX120E promotes sugarcane growth - Chun-Yan Wei; Li Lin; Li-Jing Luo; Yong-Xiu Xing; Chun-Jin Hu; Li-Tao Yang; Yang-Rui Li; Qianli An (Biology and Fertility of Soils, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

Genetic diversity analysis of yams (Dioscorea spp.) cultivated in China using ISSR and SRAP markers - Zhi Gang Wu; Xiao Xia Li; Xin Chun Lin; Wu Jiang; Zheng Ming Tao; Nitin Mantri; Chuan Yin Fan; Xiao Qing Bao (Genetic Resources and Crop Evolution, 2014)

Generation of GGTA1 biallelic knockout pigs via zinc-finger nucleases and somatic cell nuclear transfer - Lei Bao; HaiDe Chen; UiMyong Jong; CholHo Rim; WenLing Li; XiJuan Lin; Dan Zhang; Qiong Luo; Chun Cui; HeFeng Huang; Yan Zhang; Lei Xiao; et al. (Science China Life Sciences, 2014)

Elevated Cerebral Cortical CD24 Levels in Patients and Mice with Traumatic Brain Injury: A Potential Negative Role in Nuclear Factor Kappa B/Inflammatory Factor Pathway - Wei Li; Hai-Ping Ling; Wan-Chun You; Huan-Dong Liu; Qing Sun; Meng-Liang Zhou; Wei Shen; Jin-Bing Zhao; Lin Zhu; Chun-Hua Hang (Molecular Neurobiology, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

New Evidence for the Role of Ethylene in Strawberry Fruit Ripening - Jing-Hua Sun; Jing-Jing Luo; Lin Tian; Chun-Li Li; Yu Xing; Yuan-Yue Shen (Journal of Plant Growth Regulation, 2013)

Genetic diversity and evolutionary characterization of Chinese porcine reproductive and respiratory syndrome viruses based on NSP2 and ORF5 - Jian-Kui Liu; Chun-Hua Wei; Xiao-Yan Yang; Xi-Lin Hou; AI-Ling Dai; Xiao-Hua Li; Mei-Kang Wei; Xiu-Zhen Pan (Archives of Virology, 2013)

DNA methylation alterations of upland cotton (Gossypium hirsutum) in response to cold stress - Hong Hong Fan; Jun Wei; Ting Chun Li; Zheng Peng Li; Ning Guo; Yong Ping Cai; Yi Lin (Acta Physiologiae Plantarum, 2013)

Effects of single and combined genotypes of MC4R and POU1F1 genes on two production traits in Langshan chicken - Lin Jun Yan; Xing Tang Fang; Yao Liu; Chun Lei Zhang; Xuan Xuan Liu; Jing Zhao; Jing Jing Li; Hong Chen (Molecular Biology Reports, 2013)

Reduction of connexin43 in human endothelial progenitor cells impairs the angiogenic potential - Hsueh-Hsiao Wang; Cheng-Huang Su; Yih-Jer Wu; Jiun-Yi Li; Ya-Ming Tseng; Yi-Chun Lin; Chin-Ling Hsieh; Cheng-Ho Tsai; Hung-I Yeh (Angiogenesis, 2013)

Combined action of antioxidant defense system and osmolytes in chilling shock-induced chilling tolerance in Jatropha curcas seedlings - Zhong-Guang Li; Ling-Xuan Yuan; Qiu-Lin Wang; Zhi-Liu Ding; Chun-Yan Dong (Acta Physiologiae Plantarum, 2013)

Microbial transformation of ginsenoside Rb1 to compound K by Lactobacillus paralimentarius - Lin-Hu Quan; Yeon-Ju Kim; Guan Hao Li; Kwang-Tea Choi; Deok-Chun Yang (World Journal of Microbiology and Biotechnology, 2013)

Inhibition of matrix metalloproteinase-9 expression by docosahexaenoic acid mediated by heme oxygenase 1 in 12-O-tetradecanoylphorbol-13-acetate-induced MCF-7 human breast cancer cells - Haw-Wen Chen; Che-Yi Chao; Li-Lin Lin; Chia-Yang Lu; Kai-Li Liu; Chong-Kuei Lii; Chien-Chun Li (Archives of Toxicology, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

hPNAS-4 inhibits proliferation through S phase arrest and apoptosis: underlying action mechanism in ovarian cancer cells - Lei Li; Den-bang Chen; Chao Lin; Kang Cao; Yang Wan; Xin-yu Zhao; Chun-lai Nie; Zhu Yuan; Yu-quan Wei (Apoptosis, 2013)

Genetic diversity of Bartonella quintana in macaques suggests zoonotic origin of trench fever - Hao Li; Jie‐Ying Bai; Li‐Yuan Wang; Lin Zeng; Yan‐Sheng Shi; Zheng‐Liang Qiu; Hua‐Hu Ye; Xiao‐Fei Zhang; Qing‐Bin Lu; Michael Kosoy; Wei Liu; Wu‐Chun Cao (Molecular Ecology, 2013)
Bartonella quintana is a bacterium that causes a broad spectrum of diseases in humans including trench fever. Humans were previously considered to be the primary, if not the only, reservoir hosts for B. quintana . To identify the animal reservoir and extend our understanding of the ecological and evolutionary history of B. quintana , we examined blood samples from macaques and performed multilocus sequence typing ( MLST ) analysis. We demonstrated the prevalence of B. quintana infection was common in macaques from main primate centres in mainland C hina. Overall, 18.0% (59/328) of rhesus macaques and 12.7% (39/308) of cynomolgus macaques were found to be infected with B. quintana by blood culture and/or polymerase chain reaction. The infection was more frequently identified in juvenile and young monkeys compared with adult animals. In contrast with the relatively low level of sequence divergence of B. quintana reported in humans, our investigation revealed much higher genetic diversity in nonhuman primates. We identified 44 new nucleotide variable sites and 14 novel sequence types (STs) among the B. quintana isolates by MLST analysis. Some STs were found only in cynomolgus macaques, while some others were detected only in rhesus macaques, suggesting evidence of host‐cospeciation, which were further confirmed by phylogenetic analysis and Splits decomposition analysis. Our findings suggest that trench fever may primarily be a zoonotic disease with macaques as the natural hosts.

Identification of genetic associations of SP110/MYBBP1A/RELA with pulmonary tuberculosis in the Chinese Han population - Lei Cai; Shao-Li Deng; Li Liang; Hui Pan; Jia Zhou; Mei-Yan Wang; Jun Yue; Chun-Ling Wan; Guang He; Lin He (Human Genetics, 2013)

Concurrent use of antiplatelets, anticoagulants, or digoxin with Chinese medications: a population-based cohort study - Hsin-Hui Tsai; Hsiang-Wen Lin; Chun-Ru Chien; Tsai-Chung Li (European Journal of Clinical Pharmacology, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Protection by chrysin, apigenin, and luteolin against oxidative stress is mediated by the Nrf2-dependent up-regulation of heme oxygenase 1 and glutamate cysteine ligase in rat primary hepatocytes - Chin-Shiu Huang; Chong-Kuei Lii; Ai-Hsuan Lin; Yu-Wen Yeh; Hsien-Tsung Yao; Chien-Chun Li; Tsu-Shing Wang; Haw-Wen Chen (Archives of Toxicology, 2013)

Pharmacophore modeling, virtual screening, and molecular docking studies for discovery of novel Carbonic anhydrase IX inhibitors - Chun-Lin Lu; Lu Zhou; Zi-Cheng Li; Xiang Gao; Wei Zhang (Medicinal Chemistry Research, 2012)

Cloning, expression and characterization of meso-2,3-butanediol dehydrogenase from Klebsiella pneumoniae - Gen Lin Zhang; Cui Wei Wang; Chun Li (Biotechnology Letters, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Involvement of CtBP2 in LPS-induced microglial activation - Guowei Zhang; Yaohua Yan; Lihua Kang; Qi Cao; Kaifu Ke; Xinmin Wu; Yilu Gao; Qinglei Hang; Chunmiao Li; Lin Zhu; Qin Yuan; Qiyun Wu; et al. (Journal of Molecular Histology, 2012)

Urotensin upregulates transforming growth factor-β1 expression of asthma airway through ERK-dependent pathway - Wei-xi Zhang; Ya-feng Liang; Xiao-ming Wang; Ying Nie; Lei Chong; Li Lin; Chun Chen; Chang-chong Li (Molecular and Cellular Biochemistry, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

Cervid satellite DNA and karyotypic evolution of Indian muntjac - Yueh-Chun Li; Chyi-Chyang Lin (Genes & Genomics, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Impact of simulated microgravity on microvascular endothelial cell apoptosis - Chun-Yan Kang; Lin Zou; Ming Yuan; Yang Wang; Tian-Zhi Li; Ye Zhang; Jun-Feng Wang; Yan Li; Xiao-Wei Deng; Chang-Ting Liu (European Journal of Applied Physiology, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

PPARγ Agonist Suppresses TLR4 Expression and TNF-α Production in LPS Stimulated Monocyte Leukemia Cells - Chun-Zhi Wang; Yong Zhang; Xu-Dong Li; Yuan Hu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang; Pei-Qing Liu; Jia-Jun Liu (Cell Biochemistry and Biophysics, 2011)

Effects of light quality on growth and development of protocorm-like bodies of Dendrobium officinale in vitro - Yuan Lin; Jia Li; Bo Li; Tao He; Ze Chun (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Characterization of Exserohilum rostratum, a new causal agent of banana leaf spot disease in China - Shan-Hai Lin; Si-Liang Huang; Qi-Qin Li; Chun-Jin Hu; Gang Fu; Li-Ping Qin; Yue-Feng Ma; Ling Xie; Zhen-Lu Cen; Wei-Hong Yan (Australasian Plant Pathology, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

A checklist of the cultivated plants of Yunnan (PR China) - Chun-Yan Li; Guang-Yong Zhang; Karl Hammer; Chun-Yan Yang; Chun-Lin Long (Genetic Resources and Crop Evolution, 2011)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Globular adiponectin regulates energy homeostasis through AMP-activated protein kinase–acetyl-CoA carboxylase (AMPK/ACC) pathway in the hypothalamus - Jun-Ping Wen; Chun-e Liu; Ya-Ting Hu; Gang Chen; Li-xiang Lin (Molecular and Cellular Biochemistry, 2010)

Estimation of the retainer height biomechanical contribution in posterior resin-bonded fixed partial dentures: a structural-thermal coupled finite element analysis - Wen-Jen Chang; Chun-Li Lin (Medical & Biological Engineering & Computing, 2010)

The accelerating effect and mechanism of a newly functional bio-carrier modified by redox mediators for the azo dyes decolorization - Jianbo Guo; Li Kang; Jing Lian; Jingliang Yang; Bin Yan; Zaixing Li; Chun Liu; Lin Yue (Biodegradation, 2010)

Ectopic expression of an EAR motif deletion mutant of SlERF3 enhances tolerance to salt stress and Ralstonia solanacearum in tomato - I-Chun Pan; Chia-Wen Li; Ruey-Chih Su; Chiu-Ping Cheng; Choun-Sea Lin; Ming-Tsair Chan (Planta, 2010)

Prospective variants screening of connexin genes in children with hearing impairment: genotype/phenotype correlation - Jiann-Jou Yang; Wen-Hung Wang; Yen-Chun Lin; Hsu-Huei Weng; Jen-Tsung Yang; Chung-Feng Hwang; Che-Min Wu; Shuan-Yow Li (Human Genetics, 2010)

Cloning and Characterization of p8 Homolog cDNA in the Atlantic Halibut (Hippoglossus hippoglossus) - Jia-Qing Wang; Lin-Chun Li; Sheng-Guo Lin; Zhi-Ping Wang (Biochemical Genetics, 2010)

3D Micro-Crack Propagation Simulation at Enamel/Adhesive Interface Using FE Submodeling and Element Death Techniques - Heng-Liang Liu; Chun-Li Lin; Ming-Tsung Sun; Yen-Hsiang Chang (Annals of Biomedical Engineering, 2010)

Isolation of new esters from the stems of Cinnamomum reticulatum Hay - Iung-Jr Lin; Wen-Li Lo; Yi-Chen Chia; Lee-Yu Huang; Thau-Ming Cham; Wan-Shan Tseng; Yu-Ting Yeh; Hung-Chun Yeh; Yau-Der Wang; Chung-Yi Chen (Natural Product Research, 2010)

Evidence for the Formation of the Male Gynogenetic Fish - Shaojun Liu; Qinbo Qin; Yuequn Wang; Hong Zhang; Rurong Zhao; Chun Zhang; Jing Wang; Wei Li; Lin Chen; Jun Xiao; Kaikun Luo; Min Tao; et al. (Marine Biotechnology, 2010)

Exploring Taiwanese teachers’ perceptions toward and knowledge of climatic hazard mitigation - Chun-Yen Chang; Ying-Lin Chen; Chia-Li D. Chen (Natural Hazards, 2010)

Assessment of the role of brine shrimp Artemia in white spot syndrome virus (WSSV) transmission - Jia-Song Zhang; Shuang-Lin Dong; Yun-Wei Dong; Xiang-Li Tian; Yi-Cheng Cao; Zuo-Jia Li; Dong-Chun Yan (Veterinary Research Communications, 2010)

Complex genomic organization of Indian muntjac centromeric DNA - Ya-Ming Cheng; Tzai-Shiuan Li; Lie-Jiau Hsieh; Pei-Ching Hsu; Yueh-Chun Li; Chyi-Chyang Lin (Chromosome Research, 2009)

Cloning, expression and reactivating characterization of glycerol dehydratase reactivation factor from Klebsiella pneumoniae XJPD-Li - Gen Lin Zhang; Xiao Lin Xu; Chun Li; BinBin Ma (World Journal of Microbiology and Biotechnology, 2009)

In silico cloning and characterization of p8 homolog cDNA from common urchin (Paracentrotus lividus) - Jia-Qing Wang; Jin-Cheng Han; Dai-Zong Li; Lin-Chun Li (Molecular Biology Reports, 2009)

Ameliorative effects of Vaccaria segetalis extract on osteopenia in ovariectomized rats - Chun-Ching Shih; Cheng-Hsiu Lin; Wei-Li Lin (Journal of Natural Medicines, 2009)

Gene mapping and expression analysis of a novel mutantreproduce organs absent (roa) in rice - Nan Wang; Xian-Chun Sang; Yun-Feng Li; Ying-Hua Ling; Fang-Ming Zhao; Zheng-Lin Yang; Guang-Hua He (Genes & Genomics, 2009)

A 60-s postconditioning protocol by percutaneous coronary intervention inhibits myocardial apoptosis in patients with acute myocardial infarction - Wen-Shu Zhao; Lin Xu; Le-Feng Wang; Li Zhang; Zhi-Yong Zhang; Yu Liu; Xiu-Lan Liu; Xin-Chun Yang; Liang Cui; Lin Zhang (Apoptosis, 2009)

Non-synonymous GIGYF2 variants in Parkinson’s disease from two Asian populations - Eng-King Tan; Chin-Hslen Lin; Chun-Hwei Tai; Louis C. Tan; Meng-Ling Chen; R. Li; Hui-Qin Lim; Ratnagopal Pavanni; Yih Yuen; K. M. Prakash; Yi Zhao; Ruey-Meei Wu (Human Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Salicylic acid activates artemisinin biosynthesis in Artemisia annua L. - Gao-Bin Pu; Dong-Ming Ma; Jian-Lin Chen; Lan-Qing Ma; Hong Wang; Guo-Feng Li; He-Chun Ye; Ben-Ye Liu (Plant Cell Reports, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Development of twelve polymorphic microsatellite loci in polyploid endangered Omphalogramma vincaeflora Franch. (Primulaceae) - Yuan Huang; Yong Li; Xiao Hu; Xue-Jun Ge; Chang-Qin Zhang; Chun-Lin Long (Conservation Genetics, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Anthraquinone derivatives from Micromonospora rhodorangea - Chun-Mei Xue; Li Tian; Wen-Han Lin; Zhi-Wei Deng (Natural Product Research, 2009)

Mechanical interactions of cuspal-coverage designs and cement thickness in a cusp-replacing ceramic premolar restoration: a finite element study - Yen-Hsiang Chang; Wen-Hsueng Lin; Wen-Chieh Kuo; Chia-Yu Chang; Chun-Li Lin (Medical & Biological Engineering & Computing, 2009)

Changes in estrogen receptor-α variant (ER-α36) expression during mouse ovary development and oocyte meiotic maturation - Bao-Zeng Xu; Sheng-Li Lin; Mo Li; Jia-Qiao Zhu; Sen Li; Ying-Chun Ouyang; Da-Yuan Chen; Qing-Yuan Sun (Histochemistry and Cell Biology, 2009)

Molecular characterisation of two plasmids from paulownia witches’-broom phytoplasma and detection of a plasmid-encoded protein in infected plants - Cai-Li Lin; Tao Zhou; Huai-Fang Li; Zai-Feng Fan; Yong Li; Chun-Gen Piao; Guo-Zhong Tian (European Journal of Plant Pathology, 2009)

New BZLF1 sequence variations in EBV-associated undifferentiated nasopharyngeal carcinoma in southern China - Kun-Mei Ji; Chun-Lin Li; Guang Meng; Ai-Dong Han; Xu-Li Wu (Archives of Virology, 2008)

Uptake of Different Species of Iodine by Water Spinach and Its Effect to Growth - Huan-Xin Weng; Ai-Lan Yan; Chun-Lai Hong; Lin-Li Xie; Ya-Chao Qin; Charles Q. Cheng (Biological Trace Element Research, 2008)

Bisbenzopyrans and alkaloids from the roots of Stemona cochinchinensis - Pham-Huu Dien; Li-Gin Lin; Chun-Ping Tang; Chang-Qiang Ke; Yang Ye (Natural Product Research, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

Applying the grey assessment to the evaluation system of ecological green space on greening projects in Taiwan - Li-Wei Lin; Chui-Hui Chen; Hsueh-Cherng Chang; Tzu-Chun Chen (Environmental Monitoring and Assessment, 2007)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Role of P-glycoprotein in Limiting the Brain Penetration of Glabridin, An Active Isoflavan from the Root of Glycyrrhiza glabra - Xi-Yong Yu; Shu-Guang Lin; Zhi-Wei Zhou; Xiao Chen; Jun Liang; Xue-Qing Yu; Balram Chowbay; Jing-Yuan Wen; Wei Duan; Eli Chan; Xiao-Tian Li; Jie Cao; et al. (Pharmaceutical Research, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Antioxidants and a new dihydroisocoumarins from Polygala hongkongensis Hemsl - Jian-Feng Wu; Si-Bao Chen; Jing-Chun Gao; Hao-Liang Song; Li-Jun Wu; Shi-lin Chen; Peng-Fei Tu (Natural Product Research, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Identification and phylogenetic analysis of orf virus from goats in Taiwan - Kun-Wei Chan; Jen-Wei Lin; Shu-Hwae Lee; Chih-Jung Liao; Meng-Chun Tsai; Wei-Li Hsu; Min-Liang Wong; Hung-Chang Shih (Virus Genes, 2007)

QTL mapping for economic traits based on a dense genetic map of cotton with PCR-based markers using the interspecific cross of Gossypium hirsutum × Gossypium barbadense - Dao-Hua He; Zhong-Xu Lin; Xian-Long Zhang; Yi-Chun Nie; Xiao-Ping Guo; Yan-Xin Zhang; Wu Li (Euphytica, 2007)

Over-expressed estrogen receptor-α up-regulates hTNF-α gene expression and down-regulates β-catenin signaling activity to induce the apoptosis and inhibit proliferation of LoVo colon cancer cells - Hsi-Hsien Hsu; Sue-Fei Cheng; Li-Mien Chen; Jer-Yu Liu; Chun-Hsien Chu; Yi-Jiun Weng; Zih-Ying Li; Chung-Sheng Lin; Shin-Da Lee; Wei-Wen Kuo; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2006)

Buttressing angle of the double-plating fixation of a distal radius fracture: a finite element study - Chun-Li Lin; Yu-Hao Lin; Alvin Chao-Yu Chen (Medical & Biological Engineering & Computing, 2006)

Expression analysis of the NDRG2 gene in mouse embryonic and adult tissues - Xiao-Lan Hu; Xin-Ping Liu; Yan-Chun Deng; Shu-Xin Lin; Lin Wu; Jian Zhang; Li-Feng Wang; Xiao-Bin Wang; Xia Li; Lan Shen; Yuan-Qiang Zhang; Li-Bo Yao (Cell and Tissue Research, 2006)

Cardiomyoblast apoptosis induced by insulin-like growth factor (IGF)-I resistance is IGF-II dependent and synergistically enhanced by angiotensin II - Wei-Wen Kuo; Chung-Jung Liu; Li-Ming Chen; Chieh-Hsi Wu; Chun-Hsien Chu; Jer-Yuh Liu; Min-Chi Lu; James A. Lin; Shin-Da Lee; Chih-Yang Huang (Apoptosis, 2006)

Structure and function of glucose-6-phosphate dehydrogenase-deficient variants in Chinese population - Weiying Jiang; Guolong Yu; Peng Liu; Qian Geng; Luming Chen; Qundi Lin; Xiaoqin Ren; Wenhong Ye; Yongshu He; Yibin Guo; Shan Duan; Jing Wen; et al. (Human Genetics, 2006)

Molecular Cloning and Expression of a cDNA Encoding Lon Protease from rice (Oryza sativa) - Wei Su; Changfa Lin; Jiaxue Wu; Kegui Li; Guangming He; Xiaoyin Qian; Chun Wei; Jinshui Yang (Biotechnology Letters, 2006)

Effects of aromatizable and nonaromatizable androgens on the sex inversion of red-spotted grouper (Epinephelus akaara) - Guang-Li Li; Xiao-Chun Liu; Hao-Ran Lin (Fish Physiology and Biochemistry, 2006)

Status of Biological Studies and Aquaculture Development of the Mud Crab, Scylla serrata, in China: An Experimental Ecological Studies - Wang Gui-zhong; Li Shao-jing; Zeng Chao-shu; Lin Shu-jun; Kong Xiang-hui; Ai Chun-xiang; Lin Qiong-wu (Aquaculture International, 2005)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Rapid Detection and Characterization of Surfactin-Producing Bacillus subtilis and Closely Related Species Based on PCR - Feng-Chia Hsieh; Mei-Chen Li; Tsung-Chun Lin; Suey-Sheng Kao (Current Microbiology, 2004)

Strategies for agrobiodiversity conservation and promotion: a case from Yunnan, China - Chun-Lin Long; Heng Li; Zhiqin Ouyang; Xiangyun Yang; Qin Li; Bruce Trangmar (Biodiversity and Conservation, 2003)

High polyphenol oxidase activity and low titratable acidity in browning bamboo tissue culture - Li-Chun Huang; Ya-Lin Lee; Bau-Lian Huang; Ching-I Kuo; Jei-Fu Shaw (In Vitro Cellular & Developmental Biology - Plant, 2002)

Spatial correlation analysis of crop yield in the middle and west of Jilin Province - Lin-yi Li; Zhao-li Liu; Chun-lin Li; En-pu Wan (Chinese Geographical Science, 2002)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Interstitial colocalization of two cervid satellite DNAs involved in the genesis of the Indian muntjac karyotype - Yueh-Chun Li; Charles Lee; Despina Sanoudou; Tzong-Hsiung Hsu; Shuan-Yow Li; Chyi-Chyang Lin (Chromosome Research, 2000)